Cold exposure restricts Rhyzopertha dominica F. (Coleoptera: Bostrichidae) population growth across host grains and exposure durations - Dawson E. Christensen; Yoonseong Park; Travis W. Rusch; Erin D. Scully; Alison R. Gerken (Journal of Stored Products Research, 2026)

Proceedings from Nourish Now: A science dialogue on improving adolescent health through nutrition - Mario G. Ferruzzi; Regan L. Bailey; Teresa A. Davis; Heather J. Leidy; Jamie I. Baum; Jill Castle; Angela De Leon; Eva C. Diaz; Victor L. Fulgoni; Carolyn Gunther; Leslie Kaplan; Bracha Kopstick; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Decoupled mobilization of organic carbon and nitrogen in aged wildfire ashes - Travis Numan; Abrar Shahriar; Srinidhi Lokesh; Anil Timilsina; Sudarshan Basyal; Yasaman Raeofy; Qian Zhao; Jocelyn A. Richardson; Simon R. Poulson; Vera Samburova; Yu Yang (Chemosphere, 2026)

Bee-ing similar: low diversity, no population structure, and signals of adaptation in two North Dakota bumble bees - Rhiannon Hall; Meggan A. Alston; Jason P. Harmon; Clint R. V. Otto; Travis Seaborn (Biodiversity and Conservation, 2026)
Habitat fragmentation and destruction are driving widespread declines in ecosystem function, species abundance, and genetic diversity across the globe. Among the affected taxa are bumble bees (genus Bombus ), which are essential pollinators. Bumble bee declines have been linked to anthropogenic pressures such as land-use change and climate change. To better understand how the environment is shaping bumble bee populations, we employed a landscape genetics approach to examine the genetic diversity, population structure, and potential local adaptation of two widespread species— Bombus ternarius and Bombus griseocollis —across North Dakota. From 2017–2020, 161 B. ternarius and 200 B. griseocollis bumble bees were sampled in ND across 13 and 17 sites, respectively. We found low levels of heterozygosity and inbreeding across all populations for both species, with no evidence of population structure or isolation by distance. Our results revealed signatures of potential local adaptation to climatic variables and land cover characteristics, suggesting that our species are adapted to environmental gradients across the state. Having similar results between both species across all analyses suggests that other wide-ranging bumble bees in the region may share these patterns. High connectivity can buffer short-term population losses, but low genetic diversity may constrain adaptive potential and reduce resilience to future environmental change and emerging threats. Our findings have broad applicability to other pollinators and taxa facing similar environmental pressures. Both species have populations that continually exchange genes creating widespread connectivity but are still locally shaped by adaptation.

Reducing the impact of HaHV-1 in Australian abalone: The role of age and immune priming - Jacinta R. Agius; Danielle Ackerly; Angus C. Watson; Monique L Smith; Lachlan Hulands; Joshua McIntyre; Travis Beddoe; Karla J Helbig (Journal of Invertebrate Pathology, 2026)

Rethinking microbial biopesticide development and uptake - Travis R. Glare; Andy Sheppard; Mark R. H. Hurst; Louise Thatcher; Marta Gallart; Sarina Macfadyen; Simon Law; Maureen O’Callaghan (World Journal of Microbiology and Biotechnology, 2026)
Biopesticides, pesticides based on living organisms and/or their bioactive compounds, are increasingly being used as alternatives and replacements to chemical and synthetic pesticides. This is largely due to human and environmental safety concerns, the emergence of pest resistance (collectively insect pests, weeds and diseases), and the move towards holistic pest and disease control approaches. While the number and diversity of agents used in biopesticides slowly increases, the approach to developing these products remains largely ad hoc, resulting in less than 10% success rate for development projects. Here we review the major characteristics of successful biopesticides. Our treatise focuses on the benefits of considering the entire development pathway and requirements of the intended product application before embarking on the costly process of biopesticide development and commercialisation. By a priori consideration of the characteristics of both the target pest and market, and the potential limitations of the candidate microorganism and/or its bioactives (e.g. environmental persistence, ease and cost of mass production), the development pipeline can be streamlined and targeted on projects with the greatest likelihood of success. We provide a detailed consideration of the key factors that underpin successful (or not) biopesticide development and provide decision trees to support the a priori process.

Plant Functional Traits and Vegetation Structure Explain Pollination Networks at Scale - Kendall M. Jefferys; Luísa G. Carvalheiro; Adrian González Chaves; Jacobus Petersen; Xiongjie Deng; Waira S. Machida; Katherine C. R. Baldock; Danilo Boscolo; Daniel W. Carstensen; Alice Classen; Patrícia Alves Ferreira; Breno M. Freitas; et al. (Ecology Letters, 2026)
Quantifying biotic interactions at scale is critical to understanding ecosystem functions, such as plant‐pollinator interactions. Here, we demonstrate how woody plant functional traits and vegetation structure gathered with remote sensing can aid in predicting plant‐pollinator network indices from fine to broad spatial extents. We analysed 209 tropical plant‐pollinator networks, where vegetation characteristics were generated using spectral and LiDAR data. We found that pollination network structures were correlated to plant traits reflective of drought‐adaptive strategies and nutrient availability. Networks were predicted to be more nested and less specialised with increasing leaf nitrogen content. Further, relationships between leaf thickness, photosynthetic capacity, and water content indicate that networks may be more modular and less connected under arid, high‐light conditions where plants invest in water‐conserving tissues yet maintain high photosynthetic rates. Our findings reveal plant functional strategies as underlying environmental mechanisms that structure plant‐pollinator networks, paving the way to predict interactions using remote sensing.

Health benefits of parks are more strongly associated with driving access than walking access in the contiguous United States - Mark R. Kreider; William L. Rice; Cindy S. Leary; Erin O. Semmens; R. Travis Belote; Andrew J. Larson (Landscape and Urban Planning, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Correction: Affinity Capture Elution Coupled with Cell-based Cyclic Adenosine Monophosphate Assay as a Platform Method for Detection of Neutralizing Antibodies to Incretin Molecules - Nichole A. Reynolds; Yan Q. Chen; Richard E. Higgs; Boris Calderon; Jeff W. Cramer; Nicoletta Bivi; Michael E. Hodsdon; Heather A. Bullock; Travis E. Shockley; Victoria L. Peek; Justin K. Mack; Deven Lemen; et al. (The AAPS Journal, 2026)

Influence of Environmental Factors on pH Buffering, Productivity, and Blue Carbon Storage in Contrasting Thalassia Testudinum Seagrass Meadows in La Parguera, Puerto Rico - Catherine Hernández Rodríguez; Johann Collazo Reyes; Denise Ivette Perez; Juan Gonzalez-Corredor; Johannes R. Krause; Justin E. Campbell; James W. Fourqurean; Juan Jose Cruz Motta; Travis A. Courtney (Estuaries and Coasts, 2026)

A novel approach to improve the quality of beef Longissimus lumborum frozen under electromagnetic-assisted freezing - Jordan T. Looper; Sara R. Hene; Sabrina D. Lee; Zebang Zhou; Bret N. Flanders; Travis G. O'Quinn; Morgan D. Zumbaugh; Michael D. Chao (Meat Science, 2026)

In the heat of the night: Temperature and vegetation structure disparity in habitat suitability for scaled quail - Katherine A. Travis; Caleb M. McKinney; Evan P. Tanner; Ashley M. Tanner; Fidel Hernández; Leonard A. Brennan; David G. Hewitt; Humberto L. Perotto-Baldivieso; Ryan S. Luna; R. Dwayne Elmore; John McLaughlin (Journal of Thermal Biology, 2026)

Estimating safe doses of perfluorooctane sulfonate (PFOS): an international collaboration - Michael L. Dourson; Laura C. Green; Edmund A. C. Crouch; Harvey J. Clewell; Thomas Colnot; Tony Cox; Wolfgang Dekant; Linda D. Dell; James A. Deyo; Bernard K. Gadagbui; Helmut Greim; Mahesh Rachamalla Gupta; et al. (Archives of Toxicology, 2026)

Bridging accuracy and efficiency: advancing mean radiant temperature measurement in urban ecology - Aubrey Benson; Ben R. Crawford; John M. Frank; Ariane Middel; George P. Valentine; Travis Warziniack; Melissa R. McHale (International Journal of Biometeorology, 2025)

Innovative Tree Designation Methods for a Complex Silvicultural Treatment: Costs, Efficiency and Outcomes - John D. Foppert; Neal F. Maker; Kristen M. Waring; Travis Woolley; Mark R. Nabel; Jeffrey Rainey; Joel A. Jurgens (Journal of Forestry, 2025)

From canopy to comfort: The impact of residential landscape choices on thermal dynamics in a semi-arid city - Aubrey Benson; Bianca N.I. Eskelson; Travis Warziniack; Melissa R. McHale (Urban Forestry & Urban Greening, 2025)

Motivations and barriers to integrated management of annual bluegrass in sports fields: US survey findings - David E. Ervin; George B. Frisvold; Jennifer H. Allen; Aaron J. Patton; James T. Brosnan; Rebecca Grubbs Bowling; Mathew T. Elmore; Muthukumar V. Bagavathiannan; James D. McCurdy; Travis W. Gannon; John E. Kaminski; Alec R. Kowaleski; et al. (Urban Forestry & Urban Greening, 2025)

Two is Better than One: Evaluation of Single Versus Staged Approaches for Tubular Substitution Urethroplasty with Acellular Silk Fibroin Biomaterials in Rabbits - Gokhan Gundogdu; David W. Barham; Madison Rivero; Travis Nguyen; Charlotte Morgan; Joel Gelman; Joshua R. Mauney (Tissue Engineering and Regenerative Medicine, 2025)

Evaluation of SARS-CoV-2 antibody detection methods for wild Cervidae - Joshua Hewitt; Grete Wilson-Henjum; Jeffrey C. Chandler; Aaron T. Phillips; Diego G. Diel; W. David Walter; Alec Baker; Jennifer Høy-Petersen; Guillaume Bastille-Rousseau; Tadao Kishimoto; George Wittemyer; Jeremy Alder; et al. (Preventive Veterinary Medicine, 2025)

Genome-wide association mapping of loci conferring all-stage and high-temperature adult-plant resistance to stripe rust in a global spring barley collection - Arjun Upadhaya; Meinan Wang; Nosheen Fatima; Matthew Brooke; Travis Ruff; Deven R. See; Robert Brueggeman; Xianming Chen (Theoretical and Applied Genetics, 2025)

Framework for classifying chemicals for repeat dose toxicity using NAMs - J. E. Doe; P. Botham; D. Holland; M. Fuart Gatnik; V. Giri; H. Kang; P. Kalra; S. León Pérez; S. Marty; S. Moors; R. Raeburn; E. Reale; et al. (Archives of Toxicology, 2025)
EPAA’s ‘NAM Designathon 2023’ challenge for human toxicity sought to identify a classification system capable of categorising chemicals based on their bioactivity and bioavailability properties determined using non-animal methodologies (Worth et al. 2025). The proposal is made to classify chemicals into three levels of concern: low concern could be used without restriction, medium concern requiring assessment to establish safe use levels and high concern being candidates requiring risk management (Berggren and Worth in Regul Toxicol Pharmacol 142:105431, https://doi.org/10.1016/j.yrtph.2023.105431 , 2023). We developed a NAMs based classification system for “human systemic toxicity” mainly focussed on repeat dose toxicity, similar to the assessment carried out in classification for ‘Specific Target Organ Toxicity—Repeated Exposure’ (STOT-RE) based on ECETOC’s Tiered Approach integrating three lines of evidence: In silico predictions, In vitro bioavailability and PBK modelling, In vitro bioactivity assays. The first stage employed an in silico approach, covering several toxicity endpoints across various (Q)SAR in silico models to identify indicators of toxicity. Bioavailability was categorised by simulating 14-day plasma C max predictions for a standard dose level using three TK models (Firman et al. in Arch Toxicol 96:817–830, https://doi.org/10.1007/s00204-021-03205-x , 2022). Bioactivity was categorised using a matrix with potency and severity. In vitro data were obtained from ToxCast. Potency makes use of dose response AC50 values. Severity categorisation is based on consideration of the adverse effects associated with the assays. 12 chemicals have been assessed through the framework. Overall, we have demonstrated that the matrix suggested by the EPAA Designathon can be used to categorise chemicals into three different levels of concern but there are areas still to be explored especially for the range of assays used, the framework categorisation being defined, and how such a matrix would fit into a tiered approach, pragmatically, including targeted in vivo studies.

Variety-seeking behavioral markers in an immersive virtual reality food buffet are associated with greater food and energy intake in laboratory meals - John W. Long; Paige M. Cunningham; Sara J. Maksi; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Janelle Kort; Paige Grabusky; Barbara J. Rolls; et al. (Appetite, 2025)

Regeneration Response to Shelterwood-Burn Treatments in a Dry Oak-Dominated Forest - Sarah J. Rademacher; Daniel C. Dey; John M. Kabrick; Robert W. E. Quackenbush; Michael R. Saunders; J. Travis Swaim; Christopher D. Thornton; Michael A. Jenkins (Forest Science, 2025)

Evaluation of Bi-layer Silk Fibroin Grafts for Onlay Urethroplasty in a Female Porcine Model of Long Urethral Strictures - Gokhan Gundogdu; Travis Nguyen; David W. Barham; Seyed Sharifi; Charlotte Morgan; Madison Rivero; Nuriel Sussman; Shubhang V. Rajpara; Joel Gelman; Joshua R. Mauney (Tissue Engineering and Regenerative Medicine, 2025)

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

The dynamic feasibility of resisting (R), accepting (A), or directing (D) ecological change - Amanda E. Cravens; Katherine R. Clifford; Corrine Knapp; William R. Travis (Conservation Biology, 2025)
Ecological transformations are occurring as a result of climate change, challenging traditional approaches to land management decision‐making. The resist–accept–direct (RAD) framework helps managers consider how to respond to this challenge. We examined how the feasibility of the choices to resist, accept, and direct shifts in complex and dynamic ways through time. We considered 4 distinct types of social feasibility: regulatory, financial, public, and organizational. Our commentary is grounded in literature review and the examples that exist but necessarily has speculative elements because empirical evidence on this newly emerging management strategy is scarce. We expect that resist strategies will become less feasible over time as managers encounter situations where resisting is ecologically, by regulation, financially, or publicly not feasible. Similarly, we expect that as regulatory frameworks increasingly permit their use, if costs decrease, and if the public accepts them, managers will increasingly view accept and direct strategies as more viable options than they do at present. Exploring multiple types of feasibility over time allows consideration of both social and ecological trajectories of change in tandem. Our theorizing suggested that deepening the time horizon of decision‐making allows one to think carefully about when one should adopt different approaches and how to combine them over time.

What Is a Specialist? Quantifying Host Breadth Enables Impact Prediction for Invasive Herbivores - Ashley N. Schulz; Nathan P. Havill; Travis D. Marsico; Matthew P. Ayres; Kamal J.K. Gandhi; Daniel A. Herms; Angela M. Hoover; Ruth A. Hufbauer; Andrew M. Liebhold; Kenneth F. Raffa; Kathryn A. Thomas; Patrick C. Tobin; et al. (Ecology Letters, 2025)
Herbivores are commonly classified as host specialists or generalists for various purposes, yet the definitions of these terms, and their intermediates, are often imprecise and ambiguous. We quantified host breadth for 240 non‐native, tree‐feeding insects in North America using phylogenetic diversity. We demonstrated that a partitioning of host breadth: (1) causes 67% of non‐native insects to shift from a generalist to specialist category, (2) displays a reduction in host breadth from the native to introduced range, (3) identifies an inflection point in a model predicting the likelihood of non‐native insect ecological impact, with a corresponding change in behaviour associated with specialists versus generalists, and (4) enables three models for strong prediction of whether a non‐native forest insect will cause high impacts. Together, these results highlight the primacy of how herbivore host recognition and plant defences mediate whether novel host interactions will result in high impact after invasion.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Genome-wide association study reveals effect of nsSNPs on candidate genes in rice during iron deficiency - Siddharth Panda; Annamalai Anandan; K. Mohamed Shafi; Mahantesha B. N. Naika; R. Sowdhamini; G. Vanishree; Sutapa Sarkar; Anthony J. Travis; Gareth J. Norton; Adam H. Price (Functional & Integrative Genomics, 2024)

A hierarchical model of persistent and transient growth variation applied to Lake Superior lake trout - Elizabeth Stebbins; James R. Bence; Travis O. Brenden; Michael J. Hansen (Fisheries Research, 2024)

Utica/Point Pleasant brine isotopic compositions (δ7Li, δ11B, δ138Ba) elucidate mechanisms of lithium enrichment in the Appalachian Basin - Bonnie McDevitt; Travis L. Tasker; Rachel Coyte; Madalyn S. Blondes; Brian W. Stewart; Rosemary C. Capo; J. Alexandra Hakala; Avner Vengosh; William D. Burgos; Nathaniel R. Warner (Science of The Total Environment, 2024)

Abbreviated fixed-interval interventions promote self-control in rats - Kelsey Panfil; Travis R. Smith; Lexe West; Cathryn Haas; Kimberly Kirkpatrick (Behavioural Processes, 2024)

Evaluation of Bi-layer Silk Fibroin Grafts for Inlay Vaginoplasty in a Rat Model - Travis Nguyen; Gokhan Gundogdu; Christina Bottini; Ambika K. Chaudhuri; Joshua R. Mauney (Tissue Engineering and Regenerative Medicine, 2024)

No general support for functional diversity enhancing resilience across terrestrial plant communities - Lucrecia Lipoma; Stephan Kambach; Sandra Díaz; Francesco María Sabatini; Gabriella Damasceno; Jens Kattge; Christian Wirth; Scott R. Abella; Carl Beierkuhnlein; Travis R. Belote; Markus Bernhardt‐Römermann; Dylan Craven; et al. (Global Ecology and Biogeography, 2024)
Aim Understanding the mechanisms promoting resilience in plant communities is crucial in times of increasing disturbance and global environmental change. Here, we present the first meta‐analysis evaluating the relationship between functional diversity and resilience of plant communities. Specifically, we tested whether the resilience of plant communities is positively correlated with interspecific trait variation (following the niche complementarity hypothesis) and the dominance of acquisitive and small‐size species (following the mass ratio hypothesis), and for the context‐dependent effects of ecological and methodological differences across studies. Location Global. Time Period 2004–2021. Major Taxa Studied Vascular plants. Methods We compiled a dataset of 69 independent sites from 26 studies that have quantified resilience. For each site, we calculated functional diversity indices based on the floristic composition and functional traits of the plant community (obtained from the TRY database) which we correlated with resilience of biomass and floristic composition. After transforming correlation coefficients to Fisher's Z ‐scores, we conducted a hierarchical meta‐analysis, using a multilevel random‐effects model that accounted for the non‐independence of multiple effect sizes and the effects of ecological and methodological moderators. Results In general, we found no positive functional diversity–resilience relationships of grand mean effect sizes. In contrast to our expectations, we encountered a negative relationship between resilience and trait variety, especially in woody ecosystems, whereas there was a positive relationship between resilience and the dominance of acquisitive species in herbaceous ecosystems. Finally, the functional diversity–resilience relationships were strongly affected by both ecological (biome and disturbance properties) and methodological (temporal scale, study design and resilience metric) characteristics. Main Conclusions We rejected our hypothesis of a general positive functional diversity–resilience relationship. In addition to strong context dependency, we propose that idiosyncratic effects of single resident species present in the communities before the disturbances and biological legacies could play major roles in the resilience of terrestrial plant communities.

P19-05 Framework for classifying chemicals for repeat dose toxicity using NAMs - S. León Pérez; J. Doe; P. Botham; R. Settivari; S. Marty; D. Holland; P. Kalra; S. Wijeyesakere; H. Kang; R. Landsiedel; S. Moors; V. Giri; et al. (Toxicology Letters, 2024)

A Review of Factors Potentially Contributing to the Long-Term Decline of Atlantic Salmon in the Conne River, Newfoundland, Canada - J. Brian Dempson; Travis E. Van Leeuwen; Ian R. Bradbury; Sarah J. Lehnert; David Coté; Frédéric Cyr; Christina Pretty; Nicholas I. Kelly (Reviews in Fisheries Science & Aquaculture, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Effect of accelerated aging on shelf-stability, product loss, sensory and biochemical characteristics in 2 lower quality beef cuts - Haley J. Jeneske; Colin K.Y. Chun; Larissa A. Koulicoff; Sara R. Hene; Jessie Vipham; Travis G. O'Quinn; Morgan D. Zumbaugh; Michael D. Chao (Meat Science, 2024)

An efficient solution of the multi-term multi-harmonic electron Boltzmann equation for use in global models - Joel E. Lynch; Travis R. Sippel; Shankar Subramaniam (Computer Physics Communications, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Evaluation of foliar fungicides for frogeye leaf spot control and yield protection in soybean in Arkansas - Michael Emerson; Travis R. Faske (Crop Protection, 2024)

Evaluation of LAMP for Fasciola hepatica detection from faecal samples of experimentally and naturally infected cattle - Tanjina Bari; Md. Abdullah Al Mamun; Hayley Toet; Vignesh Rathinasamy; Jo-Ann Larkins; Travis Beddoe; Terry W. Spithill; David Piedrafita; Andrew R. Greenhill (Veterinary Parasitology, 2024)

A current review of U.S. beef flavor I: Measuring beef flavor - Chris R. Kerth; Jerrad F. Legako; Dale R. Woerner; J. Chance Brooks; Jessica M. Lancaster; Travis G. O'Quinn; Mahesh Nair; Rhonda K. Miller (Meat Science, 2024)

Multiple lines of evidence point to pesticides as stressors affecting invertebrate communities in small streams in five United States regions - Lisa H. Nowell; Patrick W. Moran; Ian R. Waite; Travis S. Schmidt; Paul M. Bradley; Barbara J. Mahler; Peter C. Van Metre (Science of The Total Environment, 2024)

A current review of U.S. beef flavor II: Managing beef flavor - Travis G. O'Quinn; Jerrad F. Legako; Dale R. Woerner; Chris R. Kerth; Mahesh N. Nair; J. Chance Brooks; Jessica M. Lancaster; Rhonda K. Miller (Meat Science, 2024)

Animal-vectored nutrient flows across resource gradients influence the nature of local and meta-ecosystem functioning - Matteo Rizzuto; Shawn J. Leroux; Oswald J. Schmitz; Eric Vander Wal; Yolanda F. Wiersma; Travis R. Heckford (Ecological Modelling, 2024)

Biodiversity of the Clarion-Clipperton Fracture Zone: a worm perspective - Paulo Bonifácio; Stefanie Kaiser; Travis W. Washburn; Craig R. Smith; Annemiek Vink; Pedro Martínez Arbizu (Marine Biodiversity, 2024)

Population genomic structure of a widespread, urban‐dwelling mammal: The eastern grey squirrel ( Sciurus carolinensis ) - Nicole A. Fusco; Bradley J. Cosentino; James P. Gibbs; Maximilian L. Allen; Alexander J. Blumenfeld; George H. Boettner; Elizabeth J. Carlen; Merri Collins; Catherine Dennison; Devin DiGiacopo; André‐Philippe Drapeau Picard; Jonathan Edmonson; et al. (Molecular Ecology, 2024)
Urbanization is a persistent and widespread driver of global environmental change, potentially shaping evolutionary processes due to genetic drift and reduced gene flow in cities induced by habitat fragmentation and small population sizes. We tested this prediction for the eastern grey squirrel ( Sciurus carolinensis ), a common and conspicuous forest‐dwelling rodent, by obtaining 44K SNPs using reduced representation sequencing (ddRAD) for 403 individuals sampled across the species' native range in eastern North America. We observed moderate levels of genetic diversity, low levels of inbreeding, and only a modest signal of isolation‐by‐distance. Clustering and migration analyses show that estimated levels of migration and genetic connectivity were higher than expected across cities and forested areas, specifically within the eastern portion of the species' range dominated by urbanization, and genetic connectivity was less than expected within the western range where the landscape is fragmented by agriculture. Landscape genetic methods revealed greater gene flow among individual squirrels in forested regions, which likely provide abundant food and shelter for squirrels. Although gene flow appears to be higher in areas with more tree cover, only slight discontinuities in gene flow suggest eastern grey squirrels have maintained connected populations across urban areas in all but the most heavily fragmented agricultural landscapes. Our results suggest urbanization shapes biological evolution in wildlife species depending strongly on the composition and habitability of the landscape matrix surrounding urban areas.

Portion size affects food selection in an immersive virtual reality buffet and is related to measured intake in laboratory meals varying in portion size - John W. Long; Sara J. Pritschet; Kathleen L. Keller; Charissa S.L. Cheah; Lee Boot; Alexander Klippel; Timothy R. Brick; Caitlyn G. Edwards; Barbara J. Rolls; Travis D. Masterson (Appetite, 2023)

Range of the perfluorooctanoate (PFOA) safe dose for human health: An international collaboration - Lyle D. Burgoon; Harvey J. Clewell; Tony Cox; Wolfgang Dekant; Linda D. Dell; James A. Deyo; Michael L. Dourson; Bernard K. Gadagbui; Philip Goodrum; Laura C. Green; K. Vijayavel; Travis R. Kline; et al. (Regulatory Toxicology and Pharmacology, 2023)

Diet Quality of Young Children in the US-Affiliated Pacific’s Children’s Healthy Living (CHL) Program - Rica Dela Cruz; Rachel Novotny; Lynne R. Wilkens; Yurii B. Shvetsov; Ashley B. Yamanaka; Jean Butel; Tanisha F. Aflague; Patricia Coleman; Leslie Shallcross; Jonathan Deenik; Victoria Lee R. Mapa; Carol J. Boushey; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Sensitivity of Meloidogyne incognita to pydiflumetofen - Katherine Brown; Jesse Kelly; Travis R. Faske (Crop Protection, 2023)

Stimulatory and Inhibitory Role of Allelopathic Chlorogenic Acid in Seed Germination and Seedling Growth of Tall Fescue Grass (Festuca arundinaceae Schreb.) via pH Reprogramming - Louis Bengyella; Travis R. Russell; John E. Kaminski (Journal of Plant Growth Regulation, 2023)

Hydrology drives export and composition of carbon in a pristine tropical river - Travis W. Drake; Matti Barthel; Christian Ekemba Mbongo; Davin Mata Mpambi; Simon Baumgartner; Clement Ikene Botefa; Marijn Bauters; Martin R. Kurek; Robert G. M. Spencer; Amy M. McKenna; Negar Haghipour; Godé Lompoko Ekamba; et al. (Limnology and Oceanography, 2023)
The Ruki is a pristine blackwater tributary in the Congo Basin draining tropical lowland forest. Daily discharge and fortnightly concentrations, isotopic ratios, and molecular composition of carbon and organic matter were measured for 1 yr (2019–2020). Like the Congo River, discharge peaked from November–January, with a smaller secondary peak in June. Dissolved organic carbon (DOC), inorganic carbon (DIC), carbon dioxide ( p CO 2 ), and methane ( p CH 4 ) concentrations were high (21.3 ± 4.8 mg C L −1 , 5.8 ± 0.9 mg C L −1 , 6370 ± 1740 ppm, and 250 ± 100 ppm, respectively) and positively correlated with discharge, indicating transport limitation. Total suspended solids and particulate organic carbon (POC) concentrations were generally low (3.68 ± 1.61 mg L −1 , 0.88 ± 0.33 mg C L −1 , respectively) and varied inversely with discharge, indicating source limitation. The Ruki exported a total of 3.25 Tg C yr −1 , of which DOC, DIC, and POC comprised 76%, 20%, and 3%, respectively. This DOC flux represents ~ 20% of the annual Congo Basin flux from about 5% of its area, highlighting the high yield. Isotopic ratios of DOC and POC indicate modern C3 forest vegetation as a source, except for a few older samples potentially indicating peat inputs. The bulk molecular composition of dissolved organic matter was seasonally consistent; however, a more oxidized and aromatic assemblage occurred at high discharge, corresponding with forest vegetation, while a more aliphatic, nitrogen‐, and sulfur‐enriched assemblage was found during low discharge, corresponding with soil‐derived organic matter. Overall, these results underscore how hydrology controls C concentrations in the Ruki River and how this blackwater river contributes disproportionately to C export per unit area within the Congo Basin hydrosystem.

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Stony coral tissue loss disease accelerated shifts in coral composition and declines in reef accretion potential in the Florida Keys - Lauren T. Toth; Travis A. Courtney; Michael A. Colella; Rob R. Ruzicka (Frontiers in Marine Science, 2023)
Outbreaks of coral disease have been a dominant force shaping western Atlantic coral-reef assemblages since the late 1970s. Stony coral tissue loss disease (SCTLD) is nonetheless having an unprecedented impact in the region. Whereas numerous studies over the last decade have worked to characterize this novel pathogen and its impacts on coral populations, few have quantified its functional effects on reef ecosystems. Of particular importance is how SCTLD may be impacting the essential reef-accretion process and the myriad ecosystem services it supports. Here, we evaluated the impact of SCTLD on reef-accretion potential by estimating carbonate budgets and taxon-level carbonate production at 43 sites throughout the Florida Keys from 2016−2022. Average regional reef-accretion potential declined from an already low, but positive rate of 0.30 ± 0.16 mm y -1 (mean ± standard error) in 2016 before the disease was first observed, to a state of accretionary stasis (0.08 ± 0.12 mm y -1 ) by 2022. This 70% relative decline in reef-accretion potential was driven by the loss of reef-building corals, with significant decreases in carbonate production by massive taxa including Colpophyllia natans , Montastraea cavernosa , Pseudodiploria strigosa , Orbicella spp., and Siderastrea siderea , and increasing contributions from less susceptible, weedy taxa including Millepora spp., Agaricia spp., and Porites astreoides . In general, changes in taxon-level carbonate production following the SCTLD outbreak mirror long-term shifts in reef assemblages in response to previous stressors. One striking exception, however, is S. siderea , which had become increasingly dominant in recent decades, but declined significantly in response to SCTLD. Overall, by further decimating the already depauperate reef-building coral populations in the Florida Keys, SCTLD has caused a functionally significant shift in the composition of Florida’s coral-reef assemblages and accelerated the loss of regional reef-building capacity. The dire impacts of the disease in south Florida may serve as an early warning that the persistence of the invaluable ecological and socioeconomic functions coral reefs provide will be increasingly threatened throughout the western Atlantic in the aftermath of SCTLD.

The PAVICS-Hydro platform: A virtual laboratory for hydroclimatic modelling and forecasting over North America - Richard Arsenault; David Huard; Jean-Luc Martel; Magali Troin; Juliane Mai; François Brissette; Christian Jauvin; Long Vu; James R. Craig; Trevor J. Smith; Travis Logan; Bryan A. Tolson; et al. (Environmental Modelling & Software, 2023)

Scenario-Based Decision Analysis: Integrated scenario planning and structured decision making for resource management under climate change - Brian W. Miller; Mitchell J. Eaton; Amy J. Symstad; Gregor W. Schuurman; Imtiaz Rangwala; William R. Travis (Biological Conservation, 2023)

Experimental drier climates affect hydraulics and induce high mortality of seedlings of three northern conifer species - Morgane Urli; Catherine Périé; Nelson Thiffault; Marie R. Coyea; Steeve Pepin; Travis Logan; Alison D. Munson (Forest Ecology and Management, 2023)

Long‐term patterns in inland fish kills associated with cold‐shock and winter stress: a regional case study from Texas - Steven G. Lopez; Andrea S. Aspbury; Sarah R. Fritts; Travis Tidwell; Timothy H. Bonner (Journal of Fish Biology, 2023)
Colder water temperatures are generally regarded as a stressful period for fishes ( i.e. , winter stress syndrome), which can be exacerbated by cold‐shock stress associated with major arctic freezes. Although cold‐shock stress and mass mortalities are well documented for coastal marine fishes, few studies report the effects of winter stress or cold‐shock stress on inland fishes. The purposes of this study were to describe patterns in inland fish mortalities associated with winter stress syndrome and with cold‐shock stress in Texas as a regional example of inland fish mortalities associated with colder water temperatures. Using fish mortality reports (1969–2021) recorded by state agency biologists, colder water temperature mortalities occurred in 66% ( N = 35) of the years, with greatest percentages of the reports occurring during three major arctic freezes in 1981, 1983 and 2021. The majority of reports were from urbanized counties (79%) and from lentic habitats (56%). Seventeen taxa and 1,021,217 individuals were estimated to be killed during the 53s years. Numbers of inland fish mortalities were greater during major arctic freeze years than non‐major arctic freeze years, attributed primarily to mortalities of non‐native fishes ( e.g., blue tilapia Oreochromis aureus , suckermouth catfish Hypostomus plecostomus ). Numbers of native fish mortalities, primarily clupeids and catostomids, were not different between major arctic freeze years and non‐major arctic freezes. The 43,000 inland fish mortalities reported during major arctic freeze years are in stark contrast to the 35 million coastal marine fish mortalities. Proposed mechanisms to explain cold‐shock mortalities in coastal waters ( e.g., species within the northern extent of their range, lack of access to deeper water) are similar in inland waters, yet inland waters do not have the same level of mortalities. Consequently, the disparities between mortalities in coastal and inland waters are not readily discernable at this time.

Drivers and timing of grass carp movement within the Sandusky River, Ohio: implications to potential spawning barrier response strategy - Justin J. Bopp; Travis O. Brenden; Matthew D. Faust; Christopher S. Vandergoot; Richard T. Kraus; James J. Roberts; Lucas R. Nathan (Biological Invasions, 2023)

Towards improved conversion of wet waste to jet fuel with atomic layer deposition-coated hydrodeoxygenation catalysts - W. Wilson McNeary; Jacob H. Miller; Sean A. Tacey; Jonathan Travis; Gabriella D. Lahti; Michael B. Griffin; Katherine L. Jungjohann; Glenn Teeter; Tugce Eralp Erden; Carrie A. Farberow; Luke Tuxworth; Michael J. Watson; et al. (Chemical Engineering Journal, 2023)

Children's Dietary Intake by Early Care and Education Setting in the US Affiliated Pacific - Monica Kazlausky Esquivel; Tanisha F. Aflague; Ashley B. Yamanaka; Rachael T. Leon Guerrero; Patricia Coleman; Marie Kainoa Fialkowski; Leslie Shallcross; Travis Fleming; James Davis; Carol J. Boushey; Lynne R. Wilkens; Kathryn Braun; et al. (Journal of Nutrition Education and Behavior, 2023)

Suction causes novel tooth wear in marine mammals, with implications for feeding evolution in baleen whales - Felix G. Marx; David P. Hocking; Travis Park; Tahlia I. Pollock; William M. G. Parker; James P. Rule; Erich M. G. Fitzgerald; Alistair R. Evans (Journal of Mammalian Evolution, 2023)

Assessment of three methods to evaluate the distribution of submersed aquatic vegetation in western Lake Erie - Nicole R. King; Jenny L. Hanson; Travis J. Harrison; Patrick M. Kočovský; Christine M. Mayer (Hydrobiologia, 2023)

The role of adaptive capacity in incremental and transformative adaptation in three large U.S. Urban water systems - Lisa Dilling; Meaghan E. Daly; William R. Travis; Andrea J. Ray; Olga V. Wilhelmi (Global Environmental Change, 2023)

A spatial and temporal assessment of energy development around wilderness areas - Jocelyn L. Aycrigg; T. Ryan McCarley; Sebastian Martinuzzi; R. Travis Belote; Mackensie Bosher; Connor Bailey; Matt Reeves (Biological Conservation, 2023)

Whole genome resequencing identifies local adaptation associated with environmental variation for redband trout - Kimberly R. Andrews; Travis Seaborn; Joshua P. Egan; Matthew W. Fagnan; Daniel D. New; Zhongqi Chen; Paul A. Hohenlohe; Lisette P. Waits; Christopher C. Caudill; Shawn R. Narum (Molecular Ecology, 2023)
Aquatic ectotherms are predicted to harbour genomic signals of local adaptation resulting from selective pressures driven by the strong influence of climate conditions on body temperature. We investigated local adaptation in redband trout ( Oncorhynchus mykiss gairdneri ) using genome scans for 547 samples from 11 populations across a wide range of habitats and thermal gradients in the interior Columbia River. We estimated allele frequencies for millions of single nucleotide polymorphism loci (SNPs) across populations using low‐coverage whole genome resequencing, and used population structure outlier analyses to identify genomic regions under divergent selection between populations. Twelve genomic regions showed signatures of local adaptation, including two regions associated with genes known to influence migration and developmental timing in salmonids ( GREB1L , ROCK1 , SIX6 ). Genotype–environment association analyses indicated that diurnal temperature variation was a strong driver of local adaptation, with signatures of selection driven primarily by divergence of two populations in the northern extreme of the subspecies range. We also found evidence for adaptive differences between high‐elevation desert vs. montane habitats at a smaller geographical scale. Finally, we estimated vulnerability of redband trout to future climate change using ecological niche modelling and genetic offset analyses under two climate change scenarios. These analyses predicted substantial habitat loss and strong genetic shifts necessary for adaptation to future habitats, with the greatest vulnerability predicted for high‐elevation desert populations. Our results provide new insight into the complexity of local adaptation in salmonids, and important predictions regarding future responses of redband trout to climate change.

Boundary-Layer Processes Hindering Contemporary Numerical Weather Prediction Models - Marc Calaf; Nikki Vercauteren; Gabriel G. Katul; Marco G. Giometto; Travis J. Morrison; Fabien Margairaz; Vyacheslav Boyko; Eric R. Pardyjak (Boundary-Layer Meteorology, 2023)

Influence of study design and movement behavior on performance of open population spatial Cormack-Jolly-Seber models: application to acoustic telemetry technology - Jason L. Fischer; Travis O. Brenden; Lucas R. Nathan (Environmental Biology of Fishes, 2022)

A science-based policy for managing free-roaming cats - Christopher A. Lepczyk; David C. Duffy; David M. Bird; Michael Calver; Dmitry Cherkassky; Linda Cherkassky; Christopher R. Dickman; David Hunter; David Jessup; Travis Longcore; Scott R. Loss; Kerrie Anne T. Loyd; et al. (Biological Invasions, 2022)

Factors influencing usage of antimicrobial drugs among pastoralists in Kenya - Dennis N. Makau; Ilya Slizovskiy; Vincent Obanda; Noelle R. Noyes; James R. Johnson; Michael Oakes; Dominic Travis; Kimberly VanderWaal; George P. Omondi (Tropical Animal Health and Production, 2022)

Central arterial stiffness, wave reflection, and heart rate variability following 4-week high-intensity resistance training intervention in young active women - Sarean Harmoni A. Gaynor-Metzinger; N. Travis Triplett; Marco Meucci; Kimberly S. Fasczewski; Damon H. Flinchum; Scott R. Collier (European Journal of Applied Physiology, 2022)

Using Biological Responses to Monitor Freshwater Post-Spill Conditions over 3 years in Blacktail Creek, North Dakota, USA - Aїda M. Farag; David D. Harper; Isabelle M. Cozzarelli; Douglas B. Kent; Adam C. Mumford; Denise M. Akob; Travis Schaeffer; Luke R. Iwanowicz (Archives of Environmental Contamination and Toxicology, 2022)

The past, present, and future of coral reef growth in the Florida Keys - Lauren T. Toth; Travis A. Courtney; Michael A. Colella; Selena A. Kupfner Johnson; Robert R. Ruzicka (Global Change Biology, 2022)
Coral‐reef degradation is driving global‐scale reductions in reef‐building capacity and the ecological, geological, and socioeconomic functions it supports. The persistence of those essential functions will depend on whether coral‐reef management is able to rebalance the competing processes of reef accretion and erosion. Here, we reconstructed census‐based carbonate budgets of 46 reefs throughout the Florida Keys from 1996 to 2019. We evaluated the environmental and ecological drivers of changing budget states and compared historical trends in reef‐accretion potential to millennial‐scale baselines of accretion from reef cores and future projections with coral restoration. We found that historically, most reefs had positive carbonate budgets, and many had reef‐accretion potential comparable to the ~3 mm year −1 average accretion rate during the peak of regional reef building ~7000 years ago; however, declines in reef‐building Acropora palmata and Orbicella spp. corals following a series of thermal stress events and coral disease outbreaks resulted in a shift from positive to negative budgets for most reefs in the region. By 2019, only ~15% of reefs had positive net carbonate production. Most of those reefs were in inshore, Lower Keys patch‐reef habitats with low water clarity, supporting the hypothesis that environments with naturally low irradiance may provide a refugia from thermal stress. We caution that our estimated carbonate budgets are likely overly optimistic; comparison of reef‐accretion potential to measured accretion from reef cores suggests that, by not accounting for the role of nonbiological physical and chemical erosion, census‐based carbonate budgets may underestimate total erosion by ~1 mm year −1 (−1.15 kg CaCO 3 m −2 year −1 ). Although the present state of Florida's reefs is dire, we demonstrate that the restoration of reef‐building corals has the potential to help mitigate declines in reef accretion in some locations, which could allow some key ecosystem functions to be maintained until the threat of global climate change is addressed.

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Predicting spatially heterogeneous invasive spread: Pyracantha angustifolia invading a dry Andean valley in northern Argentina - Fiona A. Plenderleith; Valentina A. Irrazabal; David F. R. P. Burslem; Justin M. J. Travis; Priscila Ana Powell (Biological Invasions, 2022)
Understanding the drivers of invasive species spread is key to designing optimal management programmes for controlling them. Population models, parameterized from demographic and dispersal data, are useful for simulating invasion when long-term observations are lacking, which is particularly important when invasions are occurring rapidly. We aimed to understand how the spread of Pyracantha angustifolia (an invasive ornamental shrub) is influenced by heterogeneity in local conditions within a dry inter-montane valley in northwestern Argentina that is currently experiencing rapid urban expansion and concomitant reduction in cattle farming. Field surveys demonstrated that individuals growing in shrublands have a higher fecundity than those in grassland and rocky habitats. Furthermore, grazing pressure of cattle and horses substantially reduces fecundity and impacts the relationship between age and fecundity. We incorporated our field-estimated habitat and age-specific fecundities into both analytical integro-difference equation models and individual-based models to predict rates of spread across each habitat type in the presence or absence of grazing pressure. Results indicate that the rate of spread would be substantially higher in shrublands (by up to 33%) and highlight that grazing pressure can, through direct consumption of seeds by livestock, substantially depress the rate of spread (by up to 53%). These results suggest that shrubland areas in the valley are most vulnerable to invasion and that grazing may help to reduce the impact of Pyracantha. This suggests that a synergism between urban expansion and reduction in domestic livestock density contributes to the spread of an invasive species in this environment.

Defining the Realized Niche of the Two Major Clades of Trichodesmium: A Study on the West Florida Shelf - Kristina A. Confesor; Corday R. Selden; Kimberly E. Powell; Laura A. Donahue; Travis Mellett; Salvatore Caprara; Angela N. Knapp; Kristen N. Buck; P. Dreux Chappell (Frontiers in Marine Science, 2022)
The cyanobacterium Trichodesmium plays an essential role supporting ocean productivity by relieving nitrogen limitation via dinitrogen (N 2 ) fixation. The two common Trichodesmium clades, T. erythraeum and T. thiebautii , are both observed in waters along the West Florida Shelf (WFS). We hypothesized that these taxa occupy distinct realized niches, where T. thiebautii is the more oceanic clade. Samples for DNA and water chemistry analyses were collected on three separate WFS expeditions (2015, 2018, and 2019) spanning multiple seasons; abundances of the single copy housekeeping gene rnpB from both clades were enumerated via quantitative PCR. We conducted a suite of statistical analyses to assess Trichodesmium clade abundances in the context of the physicochemical data. We observed a consistent coastal vs. open ocean separation of the two clades: T. erythraeum was found in shallow waters where the concentrations of dissolved iron (dFe) and the groundwater tracer Ba were significantly higher, while T. thiebautii abundance was positively correlated with water column depth. The Loop Current intrusion in 2015 with entrained Missisippi River water brought higher dFe and elevated abundance of both clades offshore of the 50 m isobath, suggesting that both clades are subject to Fe limitation on the outer shelf. Whereas, previous work has observed that T. thiebautii is more abundant than T. erythraeum in open ocean surface waters, this is the first study to examine Trichodesmium niche differentiation in a coastal environment. Understanding the environmental niches of these two key taxa bears important implications for their contributions to global nitrogen and carbon cycling and their response to global climate change.

The Lifetime Migratory History of Anadromous Brook Trout (Salvelinus fontinalis): Insights and Risks from Pesticide-Induced Fish Kills - Scott D. Roloson; Kyle M. Knysh; Sean J. Landsman; Travis L. James; Brendan J. Hicks; Michael R. van den Heuvel (Fishes, 2022)
Brook trout populations in Prince Edward Island, Canada, have experienced over 50 pesticide-related fish kills since the 1960s. Life history evaluation of large sea-run brook trout recovered following two fish kill events was compared with a reference river using strontium:calcium otolith microchemistry. This study examined the dual hypotheses that anadromous brook trout are more likely to arise from sea-run mothers, and that freshwater entry timing makes them vulnerable to pesticide-induced fish kills. A total 89% of the fish exhibited an anadromous life history, and 77% of these were offspring of anadromous mothers, suggesting that anadromy is dominant in progeny of sea-run mothers. This study adds to our understanding of the maternal inheritance of anadromy in sea-run brook trout populations. Additionally, freshwater entry precedes the majority of fish kill events, illustrating that the overlap between migration and pesticide runoff contributes to the cumulative population risks to sea-run brook trout.

The Heat-Flux Imbalance: The Role of Advection and Dispersive Fluxes on Heat Transport Over Thermally Heterogeneous Terrain - Travis Morrison; Eric R. Pardyjak; Matthias Mauder; Marc Calaf (Boundary-Layer Meteorology, 2022)

Integrating plant stoichiometry and feeding experiments: state-dependent forage choice and its implications on body mass - Juliana Balluffi-Fry; Shawn J. Leroux; Yolanda F. Wiersma; Isabella C. Richmond; Travis R. Heckford; Matteo Rizzuto; Joanie L. Kennah; Eric Vander Wal (Oecologia, 2022)

Pentalinonsterol, a Phytosterol from Pentalinon andrieuxii, is Immunomodulatory through Phospholipase A2 in Macrophages toward its Antileishmanial Action - Sanjay Varikuti; Andrew B. Shelton; Sainath R. Kotha; Travis Gurney; Gaurav Gupta; Thomas J. Hund; James R. Fuchs; A. Douglas Kinghorn; Nidhi Srivastava; Abhay R. Satoskar; Narasimham L. Parinandi (Cell Biochemistry and Biophysics, 2022)

Associations of Behavioral Problems and White Matter Properties of the Cerebellar Peduncles in Boys and Girls Born Full Term and Preterm - Machiko Hosoki; Lisa Bruckert; Lauren R. Borchers; Virginia A. Marchman; Katherine E. Travis; Heidi M. Feldman (The Cerebellum, 2022)

Distributions of native and invasive Typha (cattail) throughout the Prairie Pothole Region of North America - Brian A. Tangen; Sheel Bansal; Joanna R. Freeland; Steven E. Travis; Jennifer D. Wasko; Terence P. McGonigle; L. Gordon Goldsborough; Keira Gow; Joy E. Marburger; Jacob A. Meier (Wetlands Ecology and Management, 2022)

Olfactory responses of Argentine stem weevil to herbivory and endophyte-colonisation in perennial ryegrass - Louise M. Hennessy; Alison J. Popay; Travis R. Glare; Sarah C. Finch; Vanessa M. Cave; Michael Rostás (Journal of Pest Science, 2022)
Argentine stem weevil adults (ASW, Listronotus bonariensis ) feed on the leaves of agricultural grasses and their larvae mine the pseudostem, causing extensive damage that can result in plant death. Plants emit volatiles that serve as signals to host-searching insects and these odours can be altered by both herbivory and fungal endophyte-infection. This study investigated whether ASW adults utilise olfaction to identify their host plants, perennial ryegrass ( Lolium perenne ), and if conspecific herbivory or the presence of Epichloë festucae var. lolii fungal endophytes (strain wild-type or AR1) influenced such responses. Results from olfactometer bioassays established that ASW adults were able to utilise their olfactory response to orient towards volatiles released by perennial ryegrass and further, the weevils displayed a preference for plants previously damaged by conspecific weevils. However, there was no evidence that weevils had the ability to distinguish between endophyte-infected and endophyte-free plants using olfaction alone. Using a push–pull extraction technique, thirteen volatile compounds were identified in the blend released by perennial ryegrass. Endophyte and herbivory were found to alter these volatile compounds and quantities emitted by this forage grass. This study suggests that despite observing differences in the plant volatile blend, ASW do not perceive endophyte (wild-type and AR1) using olfaction alone and must rely on other cues, e.g. contact chemoreception or post-ingestional malaise, to detect the presence of a bioactive endophyte in an otherwise acceptable host plant.

Predicting non-native insect impact: focusing on the trees to see the forest - Ashley N. Schulz; Angela M. Mech; Matthew P. Ayres; Kamal J. K. Gandhi; Nathan P. Havill; Daniel A. Herms; Angela M. Hoover; Ruth A. Hufbauer; Andrew M. Liebhold; Travis D. Marsico; Kenneth F. Raffa; Patrick C. Tobin; et al. (Biological Invasions, 2021)

Diversity of the insect pathogenic fungi in the genus Metarhizium in New Zealand - Travis R. Glare; Yvonne Scholte Op Reimer; Nicholas Cummings; Federico Rivas‐Franco; Tracey L. Nelson; Gisbert Zimmermann (New Zealand Journal of Botany, 2021)
Invertebrate‐pathogenic fungi in the genus Metarhizium are commonly found throughout the world on a wide range of different arthropod hosts. Some strains have been developed as biopesticides and many others have shown potential for controlling important insect pests. Given the current interest in using these fungi, precise identification at species level is crucial, both for understanding their diversity and ecology and for regulatory approval and monitoring of new biopesticides. Metarhizium has undergone extensive systematic revision over the last decade, resulting in a large number of name changes and new species. This has created regulatory issues in New Zealand and importation of biocontrol strains has become difficult due to a lack of knowledge of which Metarhizium species are present in the country. This study identified Metarhizium isolates held in culture collections in New Zealand following analysis of sequence data from the ef‐1α , β‐tubulin, rpb1 , and ITS regions. Our results show that M. anisopliae , M. brunneum , M. frigidum, M. novozealandicum , M. pemphigi , M. rileyi and M. robertsii occur naturally in New Zealand on native and introduced insect hosts. Exotic Metarhizium species from several countries, stored in New Zealand collections, include M. acridum, M. lepidiotae , M. majus and M. pingshaense .

Predicting how climate change threatens the prey base of Arctic marine predators - Katie R. N. Florko; Travis C. Tai; William W. L. Cheung; Steven H. Ferguson; U. Rashid Sumaila; David J. Yurkowski; Marie Auger‐Méthé (Ecology Letters, 2021)
Arctic sea ice loss has direct consequences for predators. Climate‐driven distribution shifts of native and invasive prey species may exacerbate these consequences. We assessed potential changes by modelling the prey base of a widely distributed Arctic predator (ringed seal; Pusa hispida ) in a sentinel area for change (Hudson Bay) under high‐ and low‐greenhouse gas emission scenarios from 1950 to 2100. All changes were relatively negligible under the low‐emission scenario, but under the high‐emission scenario, we projected a 50% decline in the abundance of the well‐distributed, ice‐adapted and energy‐rich Arctic cod ( Boreogadus saida ) and an increase in the abundance of smaller temperate‐associated fish in southern and coastal areas. Furthermore, our model predicted that all fish species declined in mean body size, but a 29% increase in total prey biomass. Declines in energy‐rich prey and restrictions in their spatial range are likely to have cascading effects on Arctic predators.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Forage stoichiometry predicts the home range size of a small terrestrial herbivore - Matteo Rizzuto; Shawn J. Leroux; Eric Vander Wal; Isabella C. Richmond; Travis R. Heckford; Juliana Balluffi-Fry; Yolanda F. Wiersma (Oecologia, 2021)

Linear extension, skeletal density, and calcification rates of the blue coral Heliopora coerulea - Travis A. Courtney; James R. Guest; Alasdair J. Edwards; Romeo M. Dizon (Coral Reefs, 2021)
The brooding reef-building octocoral Heliopora is widespread on Indo-West Pacific reefs and appears to be relatively resistant to thermal stress, which may enable it to persist locally while scleractinians diminish under Anthropocene conditions. However, basic physiological measurements of “blue corals” are lacking and prevent their inclusion in trait-based studies. We address this by quantifying rates (mean ± SE) of linear extension (0.86 ± 0.05 cm yr −1 ) and skeletal density (2.01 ± 0.06 g cm −3 ) to estimate calcification rates (0.87 ± 0.08 g cm −2 yr −1 ) for the small branching/columnar morphology of Heliopora coerulea . We postulate that H. coerulea may become an increasingly important reef-builder under ocean warming due to its relative resistance to thermal stress and high skeletal density that make colonies less vulnerable to storm damage under ocean acidification. Moreover, Heliopora corals are likely dispersal limited suggesting they may be an underappreciated genus for restoration of stress-tolerant reef-building capacity on degraded reefs.

An extensive (and free) overview of invasive species biology, management, and policy in the U.S - R. Travis Belote (Biological Invasions, 2021)

Identifying Policy-relevant Indicators for Assessing Landscape Vegetation Patterns to Inform Planning and Management on Multiple-use Public Lands - Sarah K. Carter; L. E. Burris; Christopher T. Domschke; Steven L. Garman; Travis Haby; Benjamin R. Harms; E. Kachergis; S. E. Litschert; Kevin H. Miller (Environmental Management, 2021)
Understanding the structure and composition of landscapes can empower agencies to effectively manage public lands for multiple uses while sustaining land health. Many landscape metrics exist, but they are not often used in public land decision-making. Our objectives were to (1) develop and (2) apply a process for identifying a core set of indicators that public land managers can use to understand landscape-level resource patterns on and around public lands. We first developed a process for identifying indicators that are grounded in policy, feasible to quantify using existing data and resources, and useful for managers. We surveyed landscape monitoring efforts by other agencies, gathered science and agency input on monitoring goals, and quantified the prevalence of potential indicators in agency land health standards to identify five landscape indicators: amount, distribution, patch size, structural connectivity, and diversity of vegetation types. We then conducted pilot applications in four bureau of land management (BLM) field offices in Arizona, California, and Colorado to refine procedures for quantifying the indicators and assess the utility of the indicators for managers. Results highlighted the dominance of upland and the limited extent of riparian/wetland vegetation communities, moderate connectivity of priority vegetation patches, and lower diversity of native vegetation types on BLM compared to non-BLM lands. Agency staff can use the indicators to inform the development of quantitative resource management objectives in land use plans, evaluate progress in meeting those objectives, quantify potential impacts of proposed actions, and as a foundation for an all-lands approach to landscape-level management across public lands.

Evolution of virulence in a novel family of transmissible mega‐plasmids - Thomas L. Sitter; Amy L. Vaughan; Marion Schoof; Simon A. Jackson; Travis R. Glare; Murray P. Cox; Peter C. Fineran; Paul P. Gardner; Mark R. H. Hurst (Environmental Microbiology, 2021)
Summary Some Serratia entomophila isolates have been successfully exploited in biopesticides due to their ability to cause amber disease in larvae of the Aotearoa (New Zealand) endemic pasture pest, Costelytra giveni . Anti‐feeding prophage and ABC toxin complex virulence determinants are encoded by a 153‐kb single‐copy conjugative plasmid (pADAP; a mber d isease‐ a ssociated p lasmid). Despite growing understanding of the S . entomophila pADAP model plasmid, little is known about the wider plasmid family. Here, we sequence and analyse mega‐plasmids from 50 Serratia isolates that induce variable disease phenotypes in the C . giveni insect host. Mega‐plasmids are highly conserved within S . entomophila , but show considerable divergence in Serratia proteamaculans with other variants in S . liquefaciens and S . marcescens , likely reflecting niche adaption. In this study to reconstruct ancestral relationships for a complex mega‐plasmid system, strong co‐evolution between Serratia species and their plasmids were found. We identify 12 distinct mega‐plasmid genotypes, all sharing a conserved gene backbone, but encoding highly variable accessory regions including virulence factors, secondary metabolite biosynthesis, Nitrogen fixation genes and toxin‐antitoxin systems. We show that the variable pathogenicity of Serratia isolates is largely caused by presence/absence of virulence clusters on the mega‐plasmids, but notably, is augmented by external chromosomally encoded factors.

Ontogenetic Patterns of Elemental Tracers in the Vertebrae Cartilage of Coastal and Oceanic Sharks - Mariah C. Livernois; John A. Mohan; Thomas C. TinHan; Travis M. Richards; Brett J. Falterman; Nathan R. Miller; R. J. David Wells (Frontiers in Marine Science, 2021)
As predators, coastal and oceanic sharks play critical roles in shaping ecosystem structure and function, but most shark species are highly susceptible to population declines. Effective management of vulnerable shark populations requires knowledge of species-specific movement and habitat use patterns. Since sharks are often highly mobile and long-lived, tracking their habitat use patterns over large spatiotemporal scales is challenging. However, the analysis of elemental tracers in vertebral cartilage can describe a continuous record of the life history of an individual from birth to death. This study examined trace elements (Li, Mg, Mn, Zn, Sr, and Ba) along vertebral transects of five shark species with unique life histories. From most freshwater-associated to most oceanic, these species include Bull Sharks ( Carcharhinus leucas ), Bonnethead Sharks ( Sphyrna tiburo ), Blacktip Sharks ( Carcharhinus limbatus ), Spinner Sharks ( Carcharhinus brevipinna ), and Shortfin Mako Sharks ( Isurus oxyrinchus ). Element concentrations were compared across life stages (young-of-the-year, early juvenile, late juvenile, and adult) to infer species-specific ontogenetic patterns of habitat use and movement. Many of the observed elemental patterns could be explained by known life history traits: C. leucas exhibited clear ontogenetic changes in elemental composition matching expected changes in their use of freshwater habitats over time. S. tiburo elemental composition did not differ across ontogeny, suggesting residence in estuarine/coastal regions. The patterns of elemental composition were strikingly similar between C. brevipinna and C. limbatus , suggesting they co-occur in similar habitats across ontogeny. I. oxyrinchus elemental composition was stable over time, but some ontogenetic shifts occurred that may be due to changes in migration patterns with maturation. The results presented in this study enhance our understanding of the habitat use and movement patterns of coastal and oceanic sharks, and highlights the applicability of vertebral chemistry as a tool for characterizing shark life history traits.

Megafaunal Ecology of the Western Clarion Clipperton Zone - Jennifer M. Durden; Meagan Putts; Sarah Bingo; Astrid B. Leitner; Jeffrey C. Drazen; Andrew J. Gooday; Daniel O. B. Jones; Andrew K. Sweetman; Travis W. Washburn; Craig R. Smith (Frontiers in Marine Science, 2021)
The Clarion Clipperton Zone (CCZ) is a vast area of the central Pacific Ocean where the abyssal seabed is a focus for future polymetallic nodule mining. Broad-scale environmental gradients occur east-to-west across the CCZ seabed, including organic matter supply and nodule abundance, factors that influence benthic faunal community structure and function. A network of protected areas across the CCZ, called Areas of Particular Environmental Interest (APEIs), has been designated to cover this variation. Most previous studies of the benthic environment and megafaunal communities have focussed on the eastern CCZ, leaving the impact of these large-scale gradients unexamined and the network design untested. Seamounts are a further source of heterogeneity in the region. We examined the benthic megafaunal ecology of three APEIs in the western CCZ, spanning a range of environmental conditions. We used a combination of seabed photography and direct sampling to assess the environment and megafauna on the soft sediment habitats on the abyssal plain in three APEIs, and seamounts in two of those APEIs. We found that environmental conditions on abyssal plains differed between the three APEIs in terms of water depth, nodule abundance and coverage, sediment particle size distribution, and estimated organic matter flux. Megafauna were low density and high diversity, with few common morphotypes between sites and many morphotypes being observed only once. Xenophyophores dominated the assemblages. The density and diversity of invertebrates were greater at the sites with lower organic matter inputs and greater nodule abundance. Seamounts in the same APEIs were nodule-free and had coarser sediments than on the plain. Invertebrate megafaunal diversity was lower on the seamounts than on the plains, and most morphotypes recorded on the seamounts were only found on seamounts. Low morphotype overlap also suggests little connectivity between APEIs, and between seamounts and adjacent abyssal plains. Our results provide the first evaluation of the seabed habitats and megafaunal ecology in the western CCZ, highlighting environmental gradients that influence benthic communities, and are important for evaluating the design of the network of protected areas.

Strandings provide insight into social group structure of Atlantic white‐sided dolphins - Katie R. Pugliares‐Bonner; Kate LaSpina; Kathryn S. Rose; Steven E. Travis; Kristina M. Cammen (Marine Mammal Science, 2021)
Atlantic white‐sided dolphins ( Lagenorhynchus acutus ) are highly social odontocetes with a poorly understood tendency to mass strand. With limited capacity to study social ecology in the open ocean, mass strandings provide an opportunity to improve our understanding of group structure. Our study of 32 mass stranding events that occurred on Cape Cod, Massachusetts, between 1999 and 2009 identifies aspects of social ecology that vary across the year. A greater number of mass stranding events occurred outside of the breeding season and there was evidence of age‐structuring during the breeding season. We find generally low average intragroup pairwise relatedness assessed across eight microsatellite loci in a subset of 16 mass stranding events. Mass stranded groups do not show higher than expected relatedness when compared to a baseline estimate derived from single‐stranded individuals. Overall, our integration of genetic estimates of relatedness with data on sex and maturity‐class from stranded specimens suggests that Atlantic white‐sided dolphins fall near the more fluid end of the continuum from short‐term, highly fluid social associations to long‐term, stable groups represented among the odontocetes. Despite their tendency to mass strand, stable, kin‐based associations are not a defining feature of social group structure in this species.

A model of feedforward, global, and lateral inhibition in the locust visual system predicts responses to looming stimuli - Erik G. N. Olson; Travis K. Wiens; John R. Gray (Biological Cybernetics, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Hippocampal and Prefrontal Cortical Brain Tissue Levels of Irisin and GDF15 Receptor Subunits in Children - Travis C. Jackson; Kiersten Gorse; Jeremy R. Herrmann; Patrick M. Kochanek (Molecular Neurobiology, 2021)
Cold-stress hormones (CSHs) stimulate thermogenesis and have direct neuroprotective effects on the brain. The obligatory receptor components of two new CSHs (irisin and growth differentiation factor-15 [GDF15]) were recently discovered. Irisin binds integrin-αV/β5 heterodimers while GDF-15 binds to the orphan receptor glial cell-derived neurotrophic factor (GDNF) family receptor α-like (GFRAL). In addition, integrin-αV/β5 was just identified as the key receptor mediating Zika virus infection in the CNS. We measured integrin-αV, integrin-β5, and GFRAL protein levels across 78 high-quality human male/female brain tissues in infants, toddlers, preschoolers, adolescent, and adults—providing the most robust analysis to date on their levels in the human cortex and hippocampus. We report that integrin-αV was detected at all ages in the prefrontal cortex with levels greatest in adults. Integrin-αV was also detected in the hippocampus in all age groups. In contrast, integrin-β5 was detected in cortex and hippocampus largely restricted to infants. Co-expression of integrin-αV/β5 in the human infant hippocampus and cortex suggests the possibility that irisin has a more robust effect on the developing vs. the adult brain and may have implications for Zika virus infection in infants and young children.

Gregariousness is associated with parasite species richness in a community of wild chimpanzees - Jessica R. Deere; Kathryn L. Schaber; Steffen Foerster; Ian C. Gilby; Joseph T. Feldblum; Kimberly VanderWaal; Tiffany M. Wolf; Dominic A. Travis; Jane Raphael; Iddi Lipende; Deus Mjungu; Anne E. Pusey; et al. (Behavioral Ecology and Sociobiology, 2021)

Population dynamics and methodological assessments from a 15-year period of Amphibian monitoring in British Columbia’s Southern Gulf Islands - Kyle R. Nelson; Morgan M. Davies; Hanna M. Thomson; Pippi T. E. S. Lawn; Katrina Kushneryk; Eleanor K. Brouard-John; Michelle Paleczny; Sibylla Helms; Virgil C. Hawkes; Travis G. Gerwing (Environmental Monitoring and Assessment, 2021)

Patterns of Macrofaunal Biodiversity Across the Clarion-Clipperton Zone: An Area Targeted for Seabed Mining - Travis W. Washburn; Lenaick Menot; Paulo Bonifácio; Ellen Pape; Magdalena Błażewicz; Guadalupe Bribiesca-Contreras; Thomas G. Dahlgren; Tomohiko Fukushima; Adrian G. Glover; Se Jong Ju; Stefanie Kaiser; Ok Hwan Yu; et al. (Frontiers in Marine Science, 2021)
Macrofauna are an abundant and diverse component of abyssal benthic communities and are likely to be heavily impacted by polymetallic nodule mining in the Clarion-Clipperton Zone (CCZ). In 2012, the International Seabed Authority (ISA) used available benthic biodiversity data and environmental proxies to establish nine no-mining areas, called Areas of Particular Environmental Interest (APEIs) in the CCZ. The APEIs were intended as a representative system of protected areas to safeguard biodiversity and ecosystem function across the region from mining impacts. Since 2012, a number of research programs have collected additional ecological baseline data from the CCZ. We assemble and analyze macrofaunal biodiversity data sets from eight studies, focusing on three dominant taxa (Polychaeta, Tanaidacea, and Isopoda), and encompassing 477 box-core samples to address the following questions: (1) How do macrofaunal abundance, biodiversity, and community structure vary across the CCZ, and what are the potential ecological drivers? (2) How representative are APEIs of the nearest contractor areas? (3) How broadly do macrofaunal species range across the CCZ region? and (4) What scientific gaps hinder our understanding of macrofaunal biodiversity and biogeography in the CCZ ? Our analyses led us to hypothesize that sampling efficiencies vary across macrofaunal data sets from the CCZ, making quantitative comparisons between studies challenging. Nonetheless, we found that macrofaunal abundance and diversity varied substantially across the CCZ, likely due in part to variations in particulate organic carbon (POC) flux and nodule abundance. Most macrofaunal species were collected only as singletons or doubletons, with additional species still accumulating rapidly at all sites, and with most collected species appearing to be new to science. Thus, macrofaunal diversity remains poorly sampled and described across the CCZ, especially within APEIs, where a total of nine box cores have been taken across three APEIs. Some common macrofaunal species ranged over 600–3000 km, while other locally abundant species were collected across ≤ 200 km. The vast majority of macrofaunal species are rare, have been collected only at single sites, and may have restricted ranges. Major impediments to understanding baseline conditions of macrofaunal biodiversity across the CCZ include: (1) limited taxonomic description and/or barcoding of the diverse macrofauna, (2) inadequate sampling in most of the CCZ, especially within APEIs, and (3) lack of consistent sampling protocols and efficiencies.

Environmental Heterogeneity Throughout the Clarion-Clipperton Zone and the Potential Representativity of the APEI Network - Travis W. Washburn; Daniel O. B. Jones; Chih-Lin Wei; Craig R. Smith (Frontiers in Marine Science, 2021)
Environmental variables such as food supply, nodule abundance, sediment characteristics, and water chemistry may influence abyssal seafloor communities and ecosystem functions at scales from meters to thousands of kilometers. Thus, knowledge of environmental variables is necessary to understand drivers of organismal distributions and community structure, and for selection of proxies for regional variations in community structure, biodiversity, and ecosystem functions. In October 2019, the Deep CCZ Biodiversity Synthesis Workshop was conducted to (i) compile recent seafloor ecosystem data from the Clarion-Clipperton Zone (CCZ), (ii) synthesize patterns of seafloor biodiversity, ecosystem functions, and potential environmental drivers across the CCZ, and (iii) assess the representativity of no-mining areas (Areas of Particular Environmental Interest, APEIs) for subregions and areas in the CCZ targeted for polymetallic nodule mining. Here we provide a compilation and summary of water column and seafloor environmental data throughout the CCZ used in the Synthesis Workshop and in many of the papers in this special volume. Bottom-water variables were relatively homogenous throughout the region while nodule abundance, sediment characteristics, seafloor topography, and particulate organic carbon flux varied across CCZ subregions and between some individual subregions and their corresponding APEIs. This suggests that additional APEIs may be needed to protect the full range of habitats and biodiversity within the CCZ.

Monitoring water status in apple trees using a sensitive morning crop water stress index* - Abdelmoneim Z. Mohamed; Yasin Osroosh; R. Troy Peters; Travis Bates; Colin S. Campbell; Francesc Ferrer‐Alegre (Irrigation and Drainage, 2021)
The crop water stress index (CWSI) has shown to be a good indicator of water status in fruit trees. Conventional CWSI measured over solar noon is widely used to monitor plant water status. This study compared the theoretical CWSI averaged over morning hours, CWSI mo , and over solar noon hours, CWSI md , of apple trees. This study also assessed their sensitivity to the changes in soil water status (soil water deficit [SWD, %] and soil water potential [SWP, kPa]) at different root zone depths. Four different types of commercial and experimental apple orchards with different characteristics growing under semi‐arid conditions in Washington State, United States, were chosen to assess CWSI mo against CWSI md sensitivity to soil water status. In some of these locations, soil water status ranged from fully watered to severely stressed (low water deficit to high water deficit). Ground‐based thermal and microclimate measurements were recorded continuously at 10‐s intervals and acquired for the 15‐min average on a daily basis throughout the study period. The linear relationship between SWD and CWSI mo at the effective root zone depth (average of 0–150 mm and 0–460 mm) resulted in a slightly higher correlation ( R 2 = 0.42–0.64, p md ( R 2 = 0.32–0.60, p mo and SWP ( R 2 = 0.38–0.69, p mo and SWD, while SWP was less correlated with CWSI md ( R 2 = 0.33–0.55, p mo and CWSI md was observed using a nadir view orientation thermal measurement. The CWSI mo showed higher sensitivity to SWP than SWD.

Observed Dispersal of Invasive Yellow Flag Iris (Iris pseudacorus) through a Saline Marine Environment and Growth in a Novel Substrate, Shell Hash - Travis G. Gerwing; Hanna M. Thomson; Eleanor K. Brouard-John; Katrina Kushneryk; Morgan M. Davies; Pippi Lawn; Kyle R. Nelson (Wetlands, 2021)

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Trophic Structure and Sources of Variation Influencing the Stable Isotope Signatures of Meso- and Bathypelagic Micronekton Fishes - Travis M. Richards; Tracey T. Sutton; R. J. David Wells (Frontiers in Marine Science, 2020)

Navigating Climate Adaptation on Public Lands: How Views on Ecosystem Change and Scale Interact with Management Approaches - Katherine R. Clifford; Laurie Yung; William R. Travis; Renee Rondeau; Betsy Neely; Imtiaz Rangwala; Nina Burkardt; Carina Wyborn (Environmental Management, 2020)
Managers are increasingly being asked to integrate climate change adaptation into public land management. The literature discusses a range of adaptation approaches, including managing for resistance, resilience, and transformation; but many strategies have not yet been widely tested. This study employed in-depth interviews and scenario-based focus groups in the Upper Gunnison Basin in Colorado to learn how public land managers envision future ecosystem change, and how they plan to utilize different management approaches in the context of climate adaptation. While many managers evoked the past in thinking about projected climate impacts and potential responses, most managers in this study acknowledged and even embraced (if reluctantly) that many ecosystems will experience regime shifts in the face of climate change. However, accepting that future ecosystems will be different from past ecosystems led managers in different directions regarding how to respond and the appropriate role of management intervention. Some felt management actions should assist and even guide ecosystems toward future conditions. Others were less confident in projections and argued against transformation. Finally, some suggested that resilience could provide a middle path, allowing managers to help ecosystems adapt to change without predicting future ecosystem states. Scalar challenges and institutional constraints also influenced how managers thought about adaptation. Lack of institutional capacity was believed to constrain adaptation at larger scales. Resistance, in particular, was considered impractical at almost any scale due to institutional constraints. Managers negotiated scalar challenges and institutional constraints by nesting different approaches both spatially and temporally.

Sub‐lethal temperature thresholds indicate acclimation and physiological limits in brook trout Salvelinus fontinalis - Scott M. Morrison; Theresa E. Mackey; Travis Durhack; Jennifer D. Jeffrey; Lilian M. Wiens; Neil J. Mochnacz; Caleb T. Hasler; Eva C. Enders; Jason R. Treberg; Ken M. Jeffries (Journal of Fish Biology, 2020)
The upper thermal tolerance of brook trout Salvelinus fontinalis was estimated using critical thermal maxima (CT max ) experiments on fish acclimated to temperatures that span the species' thermal range (5–25°C). The CT max increased with acclimation temperature but plateaued in fish acclimated to 20, 23 and 25°C. Plasma lactate was highest, and the hepato‐somatic index ( I H ) was lowest at 23 and 25°C, which suggests additional metabolic costs at those acclimation temperatures. The results suggest that there is a sub‐lethal threshold between 20 and 23°C, beyond which the fish experience reduced physiological performance.

Yellowstone Lake Ecosystem Restoration: A Case Study for Invasive Fish Management - Todd M. Koel; Jeffery L. Arnold; Patricia E. Bigelow; Travis O. Brenden; Jeffery D. Davis; Colleen R. Detjens; Philip D. Doepke; Brian D. Ertel; Hayley C. Glassic; Robert E. Gresswell; Christopher S. Guy; Drew J. MacDonald; et al. (Fishes, 2020)
Invasive predatory lake trout Salvelinus namaycush were discovered in Yellowstone Lake in 1994 and caused a precipitous decrease in abundance of native Yellowstone cutthroat trout Oncorhynchus clarkii bouvieri. Suppression efforts (primarily gillnetting) initiated in 1995 did not curtail lake trout population growth or lakewide expansion. An adaptive management strategy was developed in 2010 that specified desired conditions indicative of ecosystem recovery. Population modeling was used to estimate effects of suppression efforts on the lake trout and establish effort benchmarks to achieve negative population growth (λ 46,800 100-m net nights; this effort level was achieved in 2012 and led to a reduction in lake trout biomass. Total lake trout biomass declined from 432,017 kg in 2012 to 196,675 kg in 2019, primarily because of a 79% reduction in adults. Total abundance declined from 925,208 in 2012 to 673,983 in 2019 but was highly variable because of recruitment of age-2 fish. Overall, 3.35 million lake trout were killed by suppression efforts from 1995 to 2019. Cutthroat trout abundance remained below target levels, but relative condition increased, large individuals (> 400 mm) became more abundant, and individual weights doubled, probably because of reduced density. Continued actions to suppress lake trout will facilitate further recovery of the cutthroat trout population and integrity of the Yellowstone Lake ecosystem.

A Comparison of the Diagnostic Accuracy of in-situ and Digital Image-Based Assessments of Coral Health and Disease - John H. R. Burns; Grady Weyenberg; Travis Mandel; Sofia B. Ferreira; Drew Gotshalk; Chad K. Kinoshita; Micah J. Marshall; Nicholas A. V. Del Moral; Shane J. Murphy; Kailey H. Pascoe; Alexandra Runyan; Alexander J. Spengler; et al. (Frontiers in Marine Science, 2020)

Percussive underwater signaling in wild gray seals - David P. Hocking; Ben Burville; William M. G. Parker; Alistair R. Evans; Travis Park; Felix G. Marx (Marine Mammal Science, 2020)

Induced spawning and embryonic and early larval development of bonefish ( Albula vulpes ) - Williams R. Halstead; Sahar Mejri; Anthony C. Cianciotto; Paul S. Wills; Travis E. Van Leeuwen; Aaron J. Adams; Jonathan M. Shenker (Journal of Fish Biology, 2020)
Bonefish ( Albula vulpes L.) are a highly prized sport fish. Despite their economic importance, populations in the Florida Keys and Caribbean are in decline, with the early life history undescribed. Injections of carp pituitary extract into A. vulpes during the advanced stages of ovarian development induced ovulation and spawning. Embryos were sampled hourly until hatching into undeveloped, yolk‐sac leptocephalus larvae. These larvae survived 56 h post‐hatch, when myomeres and eyes were developing but not the mouth. These results inform future research on the reproduction and early life history of A. vulpes .

Chronic Dyrk1 Inhibition Delays the Onset of AD-Like Pathology in 3xTg-AD Mice - R. Velazquez; B. Meechoovet; A. Ow; C. Foley; A. Shaw; B. Smith; S. Oddo; C. Hulme; Travis Dunckley (Molecular Neurobiology, 2019)

The plasma metabolome as a predictor of biological aging in humans - Lawrence C. Johnson; Keli Parker; Brandon F. Aguirre; Travis G. Nemkov; Angelo D’Alessandro; Sarah A. Johnson; Douglas R. Seals; Christopher R. Martens (GeroScience, 2019)

Skeletal muscle fibre swelling contributes to force depression in rats and humans: a mechanically-skinned fibre study - Daiki Watanabe; Travis L. Dutka; Cedric R. Lamboley; Graham D. Lamb (Journal of Muscle Research and Cell Motility, 2019)

Cryptic phenology in plants: Case studies, implications, and recommendations - Loren P. Albert; Natalia Restrepo‐Coupe; Marielle N. Smith; Jin Wu; Cecilia Chavana‐Bryant; Neill Prohaska; Tyeen C. Taylor; Giordane A. Martins; Philippe Ciais; Jiafu Mao; M. Altaf Arain; Wei Li; et al. (Global Change Biology, 2019)
Plant phenology—the timing of cyclic or recurrent biological events in plants—offers insight into the ecology, evolution, and seasonality of plant‐mediated ecosystem processes. Traditionally studied phenologies are readily apparent, such as flowering events, germination timing, and season‐initiating budbreak. However, a broad range of phenologies that are fundamental to the ecology and evolution of plants, and to global biogeochemical cycles and climate change predictions, have been neglected because they are “cryptic”—that is, hidden from view (e.g., root production) or difficult to distinguish and interpret based on common measurements at typical scales of examination (e.g., leaf turnover in evergreen forests). We illustrate how capturing cryptic phenology can advance scientific understanding with two case studies: wood phenology in a deciduous forest of the northeastern USA and leaf phenology in tropical evergreen forests of Amazonia. Drawing on these case studies and other literature, we argue that conceptualizing and characterizing cryptic plant phenology is needed for understanding and accurate prediction at many scales from organisms to ecosystems. We recommend avenues of empirical and modeling research to accelerate discovery of cryptic phenological patterns, to understand their causes and consequences, and to represent these processes in terrestrial biosphere models.

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Land use is a determinant of plant pathogen alpha‐ but not beta‐diversity - Andreas Makiola; Ian A. Dickie; Robert J. Holdaway; Jamie R. Wood; Kate H. Orwin; Travis R. Glare (Molecular Ecology, 2019)
Little is known about the diversity patterns of plant pathogens and how they change with land use at a broad scale. We employed DNA metabarcoding to describe the diversity and composition of putative plant pathogen communities in three substrates (soil, roots, and leaves) across five major land uses at a national scale. Almost all plant pathogen communities (fungi, oomycetes, and bacteria) showed strong responses to land use and substrate type. Land use category could explain up to 24% of the variance in composition between communities. Alpha‐diversity (richness) of plant pathogens was consistently lower in natural forests than in agricultural systems. In planted forests, there was also generally low pathogen alpha‐diversity in soil and roots, but alpha‐diversity in leaves was high compared with most other land uses. In contrast to alpha‐diversity, differences in within‐land use beta‐diversity of plant pathogens (the predictability of plant pathogen communities within land use) were subtle. Our results show that large‐scale patterns and distributions of putative plant pathogens can be determined using metabarcoding, allowing some of the first landscape level insights into these critically important communities.

Ocean Observations in Support of Studies and Forecasts of Tropical and Extratropical Cyclones - Ricardo Domingues; Akira Kuwano-Yoshida; Patricia Chardon-Maldonado; Robert E. Todd; George Halliwell; Hyun-Sook Kim; I.-I. Lin; Katsufumi Sato; Tomoko Narazaki; Lynn K. Shay; Travis Miles; Scott Glenn; et al. (Frontiers in Marine Science, 2019)

Age-Dependent White Matter Characteristics of the Cerebellar Peduncles from Infancy Through Adolescence - Lisa Bruckert; Katie Shpanskaya; Emily S. McKenna; Lauren R. Borchers; Maya Yablonski; Tal Blecher; Michal Ben-Shachar; Katherine E. Travis; Heidi M. Feldman; Kristen W. Yeom (The Cerebellum, 2019)

Cotton (Gossypium hirsutum L.) mutants with reduced levels of palmitic acid (C16:0) in seed lipids - Corey N. Thompson; Bralie R. Hendon; Deepika Mishra; Jacob M. Rieff; Cindy C. Lowery; Kimberly C. Lambert; Travis W. Witt; Steven J. Oswalt; Efrem Bechere; C. Wayne Smith; Roy G. Cantrell; Brendan R. Kelly; et al. (Euphytica, 2019)

Non-native gastropods in high elevation horticultural facilities in Hawaii: a threat to native biodiversity - Norine W. Yeung; Wallace M. Meyer; Kenneth A. Hayes; Jaynee R. Kim; Travis J. Skelton; Robert H. Cowie (Biological Invasions, 2019)

Genetic improvement of naked-tufted seed mutants in upland cotton (Gossypium hirsutum L.) - Bralie R. Hendon; Efrem Bechere; Travis W. Witt; Brendan R. Kelly; Deepika Mishra; Dick L. Auld (Euphytica, 2019)

Microstructural properties of white matter pathways in relation to subsequent reading abilities in children: a longitudinal analysis - Lauren R. Borchers; Lisa Bruckert; Cory K. Dodson; Katherine E. Travis; Virginia A. Marchman; Michal Ben-Shachar; Heidi M. Feldman (Brain Structure and Function, 2019)

Isolation and characterization of microsatellite markers for conservation management of the endangered Great-billed Seed-finch, Sporophila maximiliani (Aves, Passeriformes), and cross-amplification in other congeners - Cesar A. B. Medolago; Mariellen C. Costa; Flávio K. Ubaid; Travis C. Glenn; Luís F. Silveira; Mercival R. Francisco (Molecular Biology Reports, 2018)

Mitochondrial polymorphisms contribute to aging phenotypes in MNX mouse models - Carolyn J. Vivian; Travis M. Hagedorn; Roy A. Jensen; Amanda E. Brinker; Danny R. Welch (Cancer and Metastasis Reviews, 2018)

Correction to: Responding to misinformation and criticisms regarding United States cat predation estimates - Scott R. Loss; Tom Will; Travis Longcore; Peter P. Marra (Biological Invasions, 2018)

Responding to misinformation and criticisms regarding United States cat predation estimates - Scott R. Loss; Tom Will; Travis Longcore; Peter P. Marra (Biological Invasions, 2018)

Genomic data indicate ubiquitous evolutionary distinctiveness among populations of California metalmark butterflies - Julian R. Dupuis; Jeffrey C. Oliver; Bryan M. T. Brunet; Travis Longcore; Jana J. Johnson; Felix A. H. Sperling (Conservation Genetics, 2018)

Incorporating Social Diversity into Wildfire Management: Proposing “Pathways” for Fire Adaptation - Travis B Paveglio; Matthew S Carroll; Amanda M Stasiewicz; Daniel R Williams; Dennis R Becker (Forest Science, 2018)

An Improved Approach for Forecasting Ecological Impacts from Future Drilling in Unconventional Shale Oil and Gas Plays - Brad D. Wolaver; Jon Paul Pierre; Svetlana A. Ikonnikova; John R. Andrews; Guinevere McDaid; Wade A. Ryberg; Toby J. Hibbitts; Charles M. Duran; Benjamin J. Labay; Travis J. LaDuc (Environmental Management, 2018)

Regular aspirin use and gene expression profiles in prostate cancer patients - Konrad H. Stopsack; Ericka M. Ebot; Mary K. Downer; Travis A. Gerke; Jennifer R. Rider; Philip W. Kantoff; Lorelei A. Mucci (Cancer Causes & Control, 2018)

Climate change communication from cities in the USA - Constantine Boussalis; Travis G. Coan; Mirya R. Holman (Climatic Change, 2018)

Clinostomum poteae n. sp. (Digenea: Clinostomidae), in the trachea of a double-crested cormorant Phalacrocorax auritus Lesson, 1831 and molecular data linking the life-cycle stages of Clinostomum album Rosser, Alberson, Woodyard, Cunningham, Pote & Griffin, 2017 in Mississippi, USA - Thomas G. Rosser; Wes A. Baumgartner; Neely R. Alberson; Travis W. Noto; Ethan T. Woodyard; D. Tommy King; David J. Wise; Matt J. Griffin (Systematic Parasitology, 2018)

Spatio‐temporal November and March snowfall trends in the Lake Michigan region - Craig A. Clark; Bharath Ganesh‐Babu; Travis J. Elless; Anthony W. Lyza; Dana M. Koning; Alexander R. Carne; Holly A. Boney; Amanda M. Sink; Justin M. Barrick (International Journal of Climatology, 2018)
This study has investigated the spatio‐temporal variability of November and March Lake Michigan snowfall for the period 1950–2013. Snowfall characteristics were assessed using time series analysis, geographic information systems, and visualization. Results indicate significant temporal decreases of November and March snowfall, peak inter‐annual variability within the lake‐effect belt, modest concurrent and lagged sensitivity to teleconnection indices, and strong dependence of snowfall on temperature. The decreased snowfall is in contrast to December–February snowfall and associated with a decreasing fraction of November and March precipitation days occurring as snow days, rather than changes in precipitation frequency. The decreasing fraction of precipitation days occurs as snowfall is consistent with synoptic‐scale disturbances producing rain rather than snow and lake‐effect rain falling in lieu of snow.

Drought timing and local climate determine the sensitivity of eastern temperate forests to drought - Loïc D'Orangeville; Justin Maxwell; Daniel Kneeshaw; Neil Pederson; Louis Duchesne; Travis Logan; Daniel Houle; Dominique Arseneault; Colin M. Beier; Daniel A. Bishop; Daniel Druckenbrod; Shawn Fraver; et al. (Global Change Biology, 2018)
Projected changes in temperature and drought regime are likely to reduce carbon (C) storage in forests, thereby amplifying rates of climate change. While such reductions are often presumed to be greatest in semi‐arid forests that experience widespread tree mortality, the consequences of drought may also be important in temperate mesic forests of Eastern North America ( ENA ) if tree growth is significantly curtailed by drought. Investigations of the environmental conditions that determine drought sensitivity are critically needed to accurately predict ecosystem feedbacks to climate change. We matched site factors with the growth responses to drought of 10,753 trees across mesic forests of ENA , representing 24 species and 346 stands, to determine the broad‐scale drivers of drought sensitivity for the dominant trees in ENA . Here we show that two factors—the timing of drought, and the atmospheric demand for water (i.e., local potential evapotranspiration; PET )—are stronger drivers of drought sensitivity than soil and stand characteristics. Drought‐induced reductions in tree growth were greatest when the droughts occurred during early‐season peaks in radial growth, especially for trees growing in the warmest, driest regions (i.e., highest PET ). Further, mean species trait values (rooting depth and ψ 50 ) were poor predictors of drought sensitivity, as intraspecific variation in sensitivity was equal to or greater than interspecific variation in 17 of 24 species. From a general circulation model ensemble, we find that future increases in early‐season PET may exacerbate these effects, and potentially offset gains in C uptake and storage in ENA owing to other global change factors.

Need for multiscale planning for conservation of urban bats - Travis Gallo; Elizabeth W. Lehrer; Mason Fidino; R. Julia Kilgour; Patrick J. Wolff; Seth B. Magle (Conservation Biology, 2018)
For over a century there have been continual efforts to incorporate nature into urban planning. These efforts (i.e., urban reconciliation) aim to manage and create habitats that support biodiversity within cities. Given that species select habitat at different spatial scales, understanding the scale at which urban species respond to their environment is critical to the success of urban reconciliation efforts. We assessed species–habitat relationships for common bat species at 50‐m, 500‐m, and 1 km spatial scales in the Chicago (U.S.A.) metropolitan area and predicted bat activity across the greater Chicago region. Habitat characteristics across all measured scales were important predictors of silver‐haired bat ( Lasionycteris noctivagans ) and eastern red bat ( Lasiurus borealis ) activity, and big brown bat ( Eptesicus fuscus ) activity was significantly lower at urban sites relative to rural sites. Open vegetation had a negative effect on silver‐haired bat activity at the 50‐m scale but a positive effect at the 500‐m scale, indicating potential shifts in the relative importance of some habitat characteristics at different scales. These results demonstrate that localized effects may be constrained by broader spatial patterns. Our findings highlight the importance of considering scale in urban reconciliation efforts and our landscape predictions provide information that can help prioritize urban conservation work.

Comparison of Recent Oil and Gas, Wind Energy, and Other Anthropogenic Landscape Alteration Factors in Texas Through 2014 - Jon Paul Pierre; Brad D. Wolaver; Benjamin J. Labay; Travis J. LaDuc; Charles M. Duran; Wade A. Ryberg; Toby J. Hibbitts; John R. Andrews (Environmental Management, 2018)

Trans-generational but not early life exposure to stressors influences offspring morphology and survival - Dustin A. S. Owen; Travis R. Robbins; Tracy Langkilde (Oecologia, 2018)

The impact of structural biology in medicine illustrated with four case studies - Tiancen Hu; Elizabeth R. Sprague; Michelle Fodor; Travis Stams; Kirk L. Clark; Sandra W. Cowan-Jacob (Journal of Molecular Medicine, 2018)

Impacts of sea-level rise on sediment microbial community structure and function in two New England salt marshes, USA - Matt R. Simon; Gregory P. Zogg; Steven E. Travis (Journal of Soils and Sediments, 2017)

Atmospheric Deposition Effects on Plankton Communities in the Eastern Mediterranean: A Mesocosm Experimental Approach - Tatiana M. Tsagaraki; Barak Herut; Eyal Rahav; Ilana R. Berman Frank; Anastasia Tsiola; Manolis Tsapakis; Antonia Giannakourou; Alexandra Gogou; Christos Panagiotopoulos; Kalliopi Violaki; Stella Psarra; Anna Lagaria; et al. (Frontiers in Marine Science, 2017)

Chronic eccentric arm cycling improves maximum upper-body strength and power - Steven J. Elmer; Dakota J. Anderson; Travis R. Wakeham; Matthew A. Kilgas; John J. Durocher; Stan L. Lindstedt; Paul C. LaStayo (European Journal of Applied Physiology, 2017)

Simulated climate adaptation in stormwater systems: evaluating the efficiency of adaptation strategies - Adam D. McCurdy; William R. Travis (Environment Systems and Decisions, 2017)

The time course of short-term hypertrophy in the absence of eccentric muscle damage - Matt S. Stock; Jacob A. Mota; Ryan N. DeFranco; Katherine A. Grue; A. Unique Jacobo; Eunhee Chung; Jordan R. Moon; Jason M. DeFreitas; Travis W. Beck (European Journal of Applied Physiology, 2017)

Automated Gait Analysis Through Hues and Areas (AGATHA): A Method to Characterize the Spatiotemporal Pattern of Rat Gait - Heidi E. Kloefkorn; Travis R. Pettengill; Sara M. F. Turner; Kristi A. Streeter; Elisa J. Gonzalez-Rothi; David D. Fuller; Kyle D. Allen (Annals of Biomedical Engineering, 2017)

Erratum to: Visions of Restoration in Fire-Adapted Forest Landscapes: Lessons from the Collaborative Forest Landscape Restoration Program - Lauren S. Urgenson; Clare M. Ryan; Charles B. Halpern; Jonathan D. Bakker; R. Travis Belote; Jerry F. Franklin; Ryan D. Haugo; Cara R. Nelson; Amy E.M. Waltz (Environmental Management, 2017)

Visions of Restoration in Fire-Adapted Forest Landscapes: Lessons from the Collaborative Forest Landscape Restoration Program - Lauren S. Urgenson; Clare M. Ryan; Charles B. Halpern; Jonathan D. Bakker; R. Travis Belote; Jerry F. Franklin; Ryan D. Haugo; Cara R. Nelson; Amy E.M. Waltz (Environmental Management, 2017)

Beauveria bassiana as an endophyte: a critical review on associated methodology and biocontrol potential - Aimee C. McKinnon; Susanna Saari; Maria E. Moran-Diez; Nicolai V. Meyling; Maya Raad; Travis R. Glare (BioControl, 2017)

Comparing Chemistry and Census-Based Estimates of Net Ecosystem Calcification on a Rim Reef in Bermuda - Travis A. Courtney; Andreas J. Andersson; Nicholas R. Bates; Andrew Collins; Tyler Cyronak; Samantha J. de Putron; Bradley D. Eyre; Rebecca Garley; Eric J. Hochberg; Rodney Johnson; Sylvia Musielewicz; Tim J. Noyes; et al. (Frontiers in Marine Science, 2016)

Cortisol and testosterone dynamics following exhaustive endurance exercise - Travis Anderson; Amy R. Lane; Anthony C. Hackney (European Journal of Applied Physiology, 2016)

Irresistible ants: exposure to novel toxic prey increases consumption over multiple temporal scales - Mark W. Herr; Travis R. Robbins; Alan Centi; Christopher J. Thawley; Tracy Langkilde (Oecologia, 2016)

Belowground interactions with aboveground consequences: Invasive earthworms and arbuscular mycorrhizal fungi - Shishir Paudel; Travis Longcore; Beau MacDonald; Melissa K. McCormick; Katalin Szlavecz; Gail W. T. Wilson; Scott R. Loss (Ecology, 2016)
A mounting body of research suggests that invasive nonnative earthworms substantially alter microbial communities, including arbuscular mycorrhizal fungi ( AMF ). These changes to AMF can cascade to affect plant communities and vertebrate populations. Despite these research advances, relatively little is known about (1) the mechanisms behind earthworms’ effects on AMF and (2) the factors that determine the outcomes of earthworm– AMF interactions (i.e., whether AMF abundance is increased or decreased and subsequent effects on plants). We predict that AMF ‐mediated effects of nonnative earthworms on ecosystems are nearly universal because (1) AMF are important components of most terrestrial ecosystems, (2) nonnative earthworms have become established in nearly every type of terrestrial ecosystem, and (3) nonnative earthworms, due to their burrowing and feeding behavior, greatly affect AMF with potentially profound concomitant effects on plant communities. We highlight the multiple direct and indirect effects of nonnative earthworms on plants and review what is currently known about the interaction between earthworms and AMF . We also illustrate how the effects of nonnative earthworms on plant– AMF mutualisms can alter the structure and stability of aboveground plant communities, as well as the vertebrate communities relying on these habitats. Integrative studies that assess the interactive effects of earthworms and AMF can provide new insights into the role that belowground ecosystem engineers play in altering aboveground ecological processes. Understanding these processes may improve our ability to predict the structure of plant and animal communities in earthworm‐invaded regions and to develop management strategies that limit the numerous undesired impacts of earthworms.

Ochratoxin A and Human Health Risk: A Review of the Evidence - Travis R. Bui-Klimke; Felicia Wu (Critical Reviews in Food Science and Nutrition, 2015)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Environmental impacts and constraints associated with the production of major food crops in Sub-Saharan Africa and South Asia - Travis W. Reynolds; Stephen R. Waddington; C. Leigh Anderson; Alexander Chew; Zoe True; Alison Cullen (Food Security, 2015)

Geographic variation in the Pine Barrens Treefrog ( H yla andersonii ): concordance of genetic, morphometric and acoustic signal data - Alexa R. Warwick; Joseph Travis; Emily Moriarty Lemmon (Molecular Ecology, 2015)
Delimiting species is important to every subfield in biology. Templeton's cohesion species concept uses genetic and ecological exchangeability to identify sets of populations that ought to be considered as the same species, and the lack of exchangeability helps determine which populations can be grouped as evolutionarily significant units (ESU) in conservation science. However, previous work assessing genetic and ecological interchangeability among populations has been limited in scope. Here, we provide a method for assessing exchangeability that incorporates multiple, independent lines of multivariate evidence in genetic, behavioural and morphological data. We use this approach to assess exchangeability across three disjunct groups of populations of the Pine Barrens Treefrog ( Hyla andersonii ) from the eastern United States. This species is considered threatened by each state in which it occurs and conservation management of this taxon requires a clearer understanding of how populations in these three regions may differ from one another. We find a strikingly concordant pattern in which the first axis of variation for each of the three types of data distinguishes populations along a latitudinal gradient and the second axis distinguishes the set of populations occurring in the Carolinas from those occurring in the New Jersey and Florida/Alabama regions. We know of no comparable data set that displays such concordance among different types of data across so large a geographic range. The overlap in trait values (i.e. exchangeability) between neighbouring regions, however, is substantial in all three types of data, which supports continued consideration of this taxon as a single species.

Systematic culling controls a climate driven, habitat modifying invader - Sean R. Tracey; Travis Baulch; Klaas Hartmann; Scott D. Ling; Vanessa Lucieer; Martin P. Marzloff; Craig Mundy (Biological Invasions, 2015)

Trophic discrimination of nitrogen stable isotopes in amino acids varies with diet quality in a marine fish - Kelton W. McMahon; Simon R. Thorrold; Travis S. Elsdon; Matthew D. McCarthy (Limnology and Oceanography, 2015)
Analysis of individual amino acid (AA) δ 15 N values is increasingly common in studies of food web architecture, movement ecology, and biogeochemical cycling. However, observations that nitrogen isotope fractionation of AAs may vary across species and trophic positions (TP) complicate the application of compound‐specific stable isotope analysis (CSIA) in studies of aquatic food webs. We reared a common estuarine fish ( Fundulus heteroclitus ) on four diets to test the hypothesis that diet composition significantly affects AA trophic discrimination factors (TDFs) derived from normalizing fractionation of trophic AAs to the canonical source AA phenylalanine. Phenylalanine showed little trophic fractionation regardless of diet composition, confirming its use as a proxy for δ 15 N values at the base of food webs. However, TDF values showed significant negative relationships with two important measures of diet quality, protein content and AA imbalance between diet and consumer. As a result, consumers feeding on high protein diets with AA compositions matching their own had significantly lower TDF values than previous literature values, while consumers feeding on contrasting low quality diets had significantly higher TDF values than previously reported. Our results provide an explanation for the apparent relationship between TDF value and TP, and highlight a significant limitation when using a single TDF value among all trophic transfers within a food web. Accurate determination of TPs using CSIA will likely require multiple TDF values across trophic levels or further exploration of other trophic AAs, such as proline, that may show less variation in TDF with diet composition than glutamic acid.

Erratum to: Coupling thermodynamic modeling and high-resolution in situ LA-ICP-MS monazite geochronology: evidence for Barrovian metamorphism late in the Grenvillian history of southeastern Ontario - Travis McCarron; Fred Gaidies; Christopher R. M. McFarlane; R. Michael Easton; Peter Jones (Mineralogy and Petrology, 2015)

Nutrient cycling in an agroforestry alley cropping system receiving poultry litter or nitrogen fertilizer - Thomas J. Sauer; Wayne K. Coblentz; Andrew L. Thomas; Kris R. Brye; David K. Brauer; J. Vaughn Skinner; J. Van Brahana; Sherri L. DeFauw; Phillip D. Hays; David C. Moffitt; James L. Robinson; Travis A. James; et al. (Nutrient Cycling in Agroecosystems, 2015)

Climate variability and the sensitivity of downstream temperature to treated wastewater discharge: a simulation analysis - Mary T. Huisenga; William R. Travis (Environment Systems and Decisions, 2015)

Novel and cross-amplified microsatellite loci for the critically endangered São Paulo marsh antwren Formicivora paludicola (Aves: Thamnophilidae) - Crisley de Camargo; Mariellen C. Costa; Glaucia C. Del Rio; H. Lisle Gibbs; Travis C. Glenn; Ujwal Bagal; Luís F. Silveira; Adriane P. Wasko; Mercival R. Francisco (Conservation Genetics Resources, 2015)

Coupling thermodynamic modeling and high-resolution in situ LA-ICP-MS monazite geochronology: evidence for Barrovian metamorphism late in the Grenvillian history of southeastern Ontario - Travis McCarron; Fred Gaidies; Christopher R. M. McFarlane; R. Michael Easton; Peter Jones (Mineralogy and Petrology, 2014)

A genetic map of Peromyscus with chromosomal assignment of linkage groups (a Peromyscus genetic map) - Jane Kenney-Hunt; Adrienne Lewandowski; Travis C. Glenn; Julie L. Glenn; Olga V. Tsyusko; Rachel J. O’Neill; Judy Brown; Clifton M. Ramsdell; Quang Nguyen; Tony Phan; Kimberly R. Shorter; Michael J. Dewey; et al. (Mammalian Genome, 2014)

Long‐term response of a Mojave Desert winter annual plant community to a whole‐ecosystem atmospheric CO 2 manipulation ( FACE ) - Stanley D. Smith; Therese N. Charlet; Stephen F. Zitzer; Scott R. Abella; Cheryl H. Vanier; Travis E. Huxman (Global Change Biology, 2014)
Desert annuals are a critically important component of desert communities and may be particularly responsive to increasing atmospheric ( CO 2 ) because of their high potential growth rates and flexible phenology. During the 10‐year life of the Nevada Desert FACE (free‐air CO 2 enrichment) Facility, we evaluated the productivity, reproductive allocation, and community structure of annuals in response to long‐term elevated ( CO 2 ) exposure. The dominant forb and grass species exhibited accelerated phenology, increased size, and higher reproduction at elevated ( CO 2 ) in a wet El Niño year near the beginning of the experiment. However, a multiyear dry cycle resulted in no increases in productivity or reproductive allocation for the remainder of the experiment. At the community level, early indications of increased dominance of the invasive Bromus rubens at elevated ( CO 2 ) gave way to an absence of Bromus in the community during a drought cycle, with a resurgence late in the experiment in response to higher rainfall and a corresponding high density of Bromus in a final soil seed bank analysis, particularly at elevated ( CO 2 ). This long‐term experiment resulted in two primary conclusions: (i) elevated ( CO 2 ) does not increase productivity of annuals in most years; and (ii) relative stimulation of invasive grasses will likely depend on future precipitation, with a wetter climate favoring invasive grasses but currently predicted greater aridity favoring native dicots.

Physical activity, sex steroid, and growth factor concentrations in pre- and post-menopausal women: a cross-sectional study within the EPIC cohort - S. Rinaldi; R. Kaaks; C. M. Friedenreich; T. J. Key; R. Travis; C. Biessy; N. Slimani; K. Overvad; J. N. Østergaard; A. Tjønneland; A. Olsen; S. Mesrine; et al. (Cancer Causes & Control, 2014)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

The effect of rate of change, variability, and extreme events on the pace of adaptation to a changing climate - William R. Travis; Mary T. Huisenga (Climatic Change, 2013)

Adiponectin Protects Against Hyperoxic Lung Injury and Vascular Leak - Sean M. Sliman; Rishi B. Patel; Jason P. Cruff; Sainath R. Kotha; Christie A. Newland; Carrie A. Schrader; Shariq I. Sherwani; Travis O. Gurney; Ulysses J. Magalang; Narasimham L. Parinandi (Cell Biochemistry and Biophysics, 2013)

Making Monitoring Count: Project Design for Active Adaptive Management - Andrew J. Larson; R. Travis Belote; Matthew A. Williamson; Gregory H. Aplet (Journal of Forestry, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Native predator eats invasive toxic prey: evidence for increased incidence of consumption rather than aversion-learning - Travis R. Robbins; Nicole A. Freidenfelds; Tracy Langkilde (Biological Invasions, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Variation in photosynthetic response to temperature in a guild of winter annual plants - Jennifer R. Gremer; Sarah Kimball; Amy L. Angert; D. Lawrence Venable; Travis E. Huxman (Ecology, 2012)
How species respond to environmental variation can have important consequences for population and community dynamics. Temperature, in particular, is one source of variation expected to strongly influence plant performance. Here, we compared photosynthetic responses to temperature across a guild of winter annual plants. Previous work in this system identified a trade‐off between relative growth rate (RGR) and water‐use efficiency (WUE) that predicts species differences in population dynamics over time, which then contribute to long‐term species coexistence. Interestingly, species with high WUE invest in photosynthetic processes that appear to maximize carbon assimilation, while high‐RGR species appear to maximize carbon gain by increasing leaf area for photosynthesis. In high‐WUE species, higher rates of carbon acquisition were associated with increased investment into light‐driven electron transport ( J max ). We tested whether such allocation allows these plants to have greater photosynthetic performance at lower temperatures by comparing the temperature sensitivity of photosynthesis across species in the community. Six species were grown in buried pots in the field, allowing them to experience natural changes in seasonal temperature. Plants were taken from the field and placed in growth chambers where photosynthetic performance was measured following short‐term exposure to a wide range of temperatures. These measurements were repeated throughout the season. Our results suggest that high‐WUE species are more efficient at processing incoming light, as measured by chlorophyll fluorescence, and exhibit higher net photosynthetic rates ( A net ) than high‐RGR species, and these advantages are greatest at low temperatures. Sampling date differentially affected fluorescence across species, while species had similar seasonal changes in A net . Our results suggest that species‐specific responses to temperature contribute to the WUE–RGR trade‐off that has been shown to promote coexistence in this community. These differential responses to environmental conditions can have important effects on fitness, population dynamics, and community structure.

Increased temperature and altered summer precipitation have differential effects on biological soil crusts in a dryland ecosystem - Shannon L. Johnson; Cheryl R. Kuske; Travis D. Carney; David C. Housman; La Verne Gallegos‐Graves; Jayne Belnap (Global Change Biology, 2012)
Biological soil crusts (biocrusts) are common and ecologically important members of dryland ecosystems worldwide, where they stabilize soil surfaces and contribute newly fixed C and N to soils. To test the impacts of predicted climate change scenarios on biocrusts in a dryland ecosystem, the effects of a 2–3 °C increase in soil temperature and an increased frequency of smaller summer precipitation events were examined in a large, replicated field study conducted in the cold desert of the C olorado P lateau, USA . Surface soil biomass ( DNA concentration), photosynthetically active cyanobacterial biomass (chlorophyll a concentration), cyanobacterial abundance (quantitative PCR assay), and bacterial community composition (16S rRNA gene sequencing) were monitored seasonally over 2 years. Soil microbial biomass and bacterial community composition were highly stratified between the 0–2 cm depth biocrusts and 5–10 cm depth soil beneath the biocrusts. The increase in temperature did not have a detectable effect on any of the measured parameters over 2 years. However, after the second summer of altered summer precipitation pattern, significant declines occurred in the surface soil biomass (avg. DNA concentration declined 38%), photosynthetic cyanobacterial biomass (avg. chlorophyll a concentration declined 78%), cyanobacterial abundance (avg. gene copies g −1 soil declined 95%), and proportion of C yanobacteria in the biocrust bacterial community (avg. representation in sequence libraries declined 85%). Biocrusts are important contributors to soil stability, soil C and N stores, and plant performance, and the loss or reduction of biocrusts under an altered precipitation pattern associated with climate change could contribute significantly to lower soil fertility and increased erosion and dust production in dryland ecosystems at a regional scale.

Cloning, functional characterization and genomic organization of 1,8-cineole synthases from Lavandula - Zerihun A. Demissie; Monica A. Cella; Lukman S. Sarker; Travis J. Thompson; Mark R. Rheault; Soheil S. Mahmoud (Plant Molecular Biology, 2012)

Fitness and physiology in a variable environment - Sarah Kimball; Jennifer R. Gremer; Amy L. Angert; Travis E. Huxman; D. Lawrence Venable (Oecologia, 2012)

Within‐plant isoprene oxidation confirmed by direct emissions of oxidation products methyl vinyl ketone and methacrolein - Kolby J. Jardine; Russell K. Monson; Leif Abrell; Scott R. Saleska; Almut Arneth; Angela Jardine; Françoise Yoko Ishida; Ana Maria Yanez Serrano; Paulo Artaxo; Thomas Karl; Silvano Fares; Allen Goldstein; et al. (Global Change Biology, 2012)
Isoprene is emitted from many terrestrial plants at high rates, accounting for an estimated 1/3 of annual global volatile organic compound emissions from all anthropogenic and biogenic sources combined. Through rapid photooxidation reactions in the atmosphere, isoprene is converted to a variety of oxidized hydrocarbons, providing higher order reactants for the production of organic nitrates and tropospheric ozone, reducing the availability of oxidants for the breakdown of radiatively active trace gases such as methane, and potentially producing hygroscopic particles that act as effective cloud condensation nuclei. However, the functional basis for plant production of isoprene remains elusive. It has been hypothesized that in the cell isoprene mitigates oxidative damage during the stress‐induced accumulation of reactive oxygen species ( ROS ), but the products of isoprene‐ ROS reactions in plants have not been detected. Using pyruvate‐2‐ 13 C leaf and branch feeding and individual branch and whole mesocosm flux studies, we present evidence that isoprene ( i ) is oxidized to methyl vinyl ketone and methacrolein ( i ox ) in leaves and that i ox /i emission ratios increase with temperature, possibly due to an increase in ROS production under high temperature and light stress. In a primary rainforest in A mazonia, we inferred significant in plant isoprene oxidation (despite the strong masking effect of simultaneous atmospheric oxidation), from its influence on the vertical distribution of i ox uptake fluxes, which were shifted to low isoprene emitting regions of the canopy. These observations suggest that carbon investment in isoprene production is larger than that inferred from emissions alone and that models of tropospheric chemistry and biota–chemistry–climate interactions should incorporate isoprene oxidation within both the biosphere and the atmosphere with potential implications for better understanding both the oxidizing power of the troposphere and forest response to climate change.

Forest Management, Engineering, and Operations - Randy Kolka; Matt Powers; John Bradford; Brian Palik; Marty Jurgensen; Dalia Abbas; Tom Gallagher; Stephen Ambagis; Finto Antony; Lewis Jordan; Richard Daniels; Laurie Schimleck; et al. (Journal of Forestry, 2011)
9Forests represent a major global C sink, and forest management strategies that maximize carbon storage offer one avenue for mitigating increases in atmospheric carbon dioxide concentrations. Our understanding of relationships between forest management, productivity, carbon storage, and stand age, however, is limited. We established research plots in a chronosequence of thinned and unmanaged red pine stands in northern Minnesota to study patterns of carbon storage, and the major fluxes that influence carbon sequestration. We completed an inventory of all major C pools across a chronosequence of 57 red pine stands ages 9-306 years on the Chippewa National Forest in the fall of 2009. Results indicate total ecosystem C pools increase as red pine stands age for at least 150 years, and on-site C storage in thinned stands appears similar to unmanaged stands of comparable ages, despite different age-related trends in the live tree and forest floor pools. Thinned stands may have the potential to store more C than unmanaged stands in old age when C removed during harvesting is added into the total ecosystem C pool.

An examination of the time course of training-induced skeletal muscle hypertrophy - Jason M. DeFreitas; Travis W. Beck; Matt S. Stock; Michael A. Dillon; Paul R. Kasishke (European Journal of Applied Physiology, 2011)

Transport of NOX Emissions from Sugarcane Fertilisation into the Great Barrier Reef Lagoon - Clare Paton-Walsh; Stephen R. Wilson; Travis Naylor; David W. T. Griffith; O. T. Denmead (Environmental Modeling & Assessment, 2011)

Entorhinal cortex volume is associated with episodic memory related brain activation in normal aging and amnesic mild cognitive impairment - Mehul A. Trivedi; Travis R. Stoub; Christopher M. Murphy; Sarah George; Leyla deToledo-Morrell; Raj C. Shah; Susan Whitfield-Gabrieli; John D. E. Gabrieli; Glenn T. Stebbins (Brain Imaging and Behavior, 2011)

Characterization of a genomic divergence island between black‐and‐yellow and gopher Sebastes rockfishes - VINCENT P. BUONACCORSI; SHAWN R. NARUM; KRISTINE A. KARKOSKA; STEVEN GREGORY; TRAVIS DEPTOLA; ALEXANDER B. WEIMER (Molecular Ecology, 2011)
Islands of high genomic divergence that contain genes of evolutionary significance may form between diverging species. The gopher rockfish, Sebastes carnatus, and black‐and‐yellow rockfish, S. chrysomelas , are sympatrically distributed temperate marine species inhabiting rocky reefs and kelp forests on the west coast of the United States. Prior studies documented low levels of genetic divergence between the two species, except at a single microsatellite locus that displayed high divergence, Sra .7‐2. To better characterize genome wide divergence, we scored 25 additional microsatellite loci. Mean neutral divergence between species ( F ST = 0.01) changed little from prior estimates. Sra .7‐2 continued to be an extreme divergence outlier. Five novel microsatellites within ± 15 kb of Sra .7‐2 were characterized. High divergence, consistently low diversity in S. chrysomelas , and linkage disequilibrium were detected at these loci, suggesting the influence of recent selection. However, coalescent modelling of divergence at neutral and Sra .7‐2 regions showed that initial divergence at Sra .7‐2 was ancient, likely predating divergence at neutral regions. It is therefore unlikely that Sra .7‐2 divergence represents solely recent ecological divergence within one species and may represent the action of recurrent selection. Introgressive gene flow (2 N E m ) was much higher (>>1) at neutral than Sra .7‐2 regions ( S. carnatus individuals have recently mixed ancestry at the Sra .7‐2 region. The Sra .7‐2 genomic region is likely one of several regions containing genes involved in initiating and maintaining species integrity. Completion of the final stages of speciation appears to be a slow and ongoing process for these species.

Subarachnoid Hemorrhage Induces Gliosis and Increased Expression of the Pro-inflammatory Cytokine High Mobility Group Box 1 Protein - Kentaro Murakami; Masayo Koide; Travis M. Dumont; Sheila R. Russell; Bruce I. Tranmer; George C. Wellman (Translational Stroke Research, 2011)

Alcohol-Induced Interactive Phosphorylation of Src and Toll-like Receptor Regulates the Secretion of Inflammatory Mediators by Human Astrocytes - Nicholas A. Floreani; Travis J. Rump; P. M. Abdul Muneer; Saleena Alikunju; Brenda M. Morsey; Michael R. Brodie; Yuri Persidsky; James Haorah (Journal of Neuroimmune Pharmacology, 2010)

Erratum to: Isolation and characterization of 14 polymorphic microsatellite DNA loci for the endangered Whooping Crane (Grus americana) and their applicability to other crane species - Kenneth L. Jones; Jessica R. Henkel; Jerome J. Howard; Stacey L. Lance; Chris Hagen; Travis C. Glenn (Conservation Genetics Resources, 2010)

Isolation and characterization of 14 polymorphic microsatellite DNA loci for the endangered Whooping Crane (Grus americana) and their applicability to other crane species - Kenneth L. Jones; Jessica R. Henkel; Jerome J. Howard; Stacey L. Lance; Chris Hagen; Travis C. Glenn (Conservation Genetics Resources, 2010)

Five hundred microsatellite loci for Peromyscus - Jesse N. Weber; Maureen B. Peters; Olga V. Tsyusko; Catherine R. Linnen; Cris Hagen; Nancy A. Schable; Tracey D. Tuberville; Anna M. McKee; Stacey L. Lance; Kenneth L. Jones; Heidi S. Fisher; Michael J. Dewey; et al. (Conservation Genetics, 2010)

Fire Burners to Firefighters: The Nez Perce and Fire - Matthew S. Carroll; Patricia J. Cohn; Travis B. Paveglio; Donna R. Drader; Pamela J. Jakes (Journal of Forestry, 2010)
This article presents results from an interview-based case study examining burning practices of the Nez Perce tribe in the Inland Northwest in both their contemporary and historical policy context. Despite the lack of a prominent fire tradition, our interviews uncovered a legacy of knowledge and cultural traditions linked to fire and a variety of contemporary fire practices on the reservation performed by land-management professionals and individual tribal members. Many of these practices, particularly those involving broadcast burning, have diminished over the years. We examine the reasons for this and the potentials for mitigating some of the practical and policy constraints to such burning. We conclude that the nontribal community still has much to learn about fire from those who have lived in fire-adapted landscapes longer than anyone else.

Going to extremes: propositions on the social response to severe climate change - William R. Travis (Climatic Change, 2010)

Human β-galactoside α-2,3-sialyltransferase (ST3Gal III) attenuated Taxol-induced apoptosis in ovarian cancer cells by downregulating caspase-8 activity - Su Huang; Travis W. Day; Mi-Ran Choi; Ahmad R. Safa (Molecular and Cellular Biochemistry, 2009)

Successive bouts of cycling stimulates genes associated with mitochondrial biogenesis - Charles L. Dumke; J. Mark Davis; E. Angela Murphy; David C. Nieman; Martin D. Carmichael; John C. Quindry; N. Travis Triplett; Alan C. Utter; Sarah J. Gross Gowin; Dru A. Henson; Steven R. McAnulty; Lisa S. McAnulty (European Journal of Applied Physiology, 2009)

Disturbance alters local–regional richness relationships in Appalachian forests - R. Travis Belote; Nathan J. Sanders; Robert H. Jones (Ecology, 2009)
Whether biological diversity within communities is limited by local interactions or regional species pools remains an important question in ecology. In this paper, we investigate how an experimentally applied tree‐harvesting disturbance gradient influenced local–regional richness relationships. Plant species richness was measured at three spatial scales (2 ha = regional; 576 m 2 and 1 m 2 = local) on three occasions (one year pre‐disturbance, one year post‐disturbance, and 10 years post‐disturbance) across five disturbance treatments (uncut control through clearcut) replicated throughout the southern Appalachian Mountains, USA. We investigated whether species richness in 576‐m 2 plots and 1‐m 2 subplots depended on species richness in 2‐ha experimental units and whether this relationship changed through time before and after canopy disturbance. We found that, before disturbance, the relationship between local and regional richness was weak or nonexistent. One year after disturbance local richness was a positive function of regional richness, because local sites were colonized from the regional species pool. Ten years after disturbance, the positive relationship persisted, but the slope had decreased by half. These results suggest that disturbance can set the stage for strong influences of regional species pools on local community assembly in temperate forests. However, as time since disturbance increases, local controls on community assembly decouple the relationships between regional and local diversity.

Fifteen polymorphic microsatellite loci from Jamaican streamertail hummingbirds (Trochilus) - Stacey L. Lance; Cris Hagen; Travis C. Glenn; Robb T. Brumfield; Katherine Faust Stryjewski; Gary R. Graves (Conservation Genetics, 2009)

Cross-species amplification of microsatellites in crocodilians: assessment and applications for the future - Lee G. Miles; Stacey L. Lance; Sally R. Isberg; Chris Moran; Travis C. Glenn (Conservation Genetics, 2009)

253 Novel polymorphic microsatellites for the saltwater crocodile (Crocodylus porosus) - Lee G. Miles; Sally R. Isberg; Chris Moran; Cris Hagen; Travis C. Glenn (Conservation Genetics, 2009)

Understanding Social Complexity Within the Wildland–Urban Interface: A New Species of Human Habitation? - Travis B. Paveglio; Pamela J. Jakes; Matthew S. Carroll; Daniel R. Williams (Environmental Management, 2009)

Effects of sibutramine and rimonabant in rats trained to discriminate between 22- and 2-h food deprivation - David C. Jewett; Thomas W. Hahn; Travis R. Smith; Britta L. Fiksdal; Jason M. Wiebelhaus; Andrew R. Dunbar; Catherine R. Filtz; Noah L. Novinska; Allen S. Levine (Psychopharmacology, 2009)

Tree leaf litter composition and nonnative earthworms influence plant invasion in experimental forest floor mesocosms - R. Travis Belote; Robert H. Jones (Biological Invasions, 2009)

Tick-borne flaviviruses: dissecting host immune responses and virus countermeasures - Shelly J. Robertson; Dana N. Mitzel; R. Travis Taylor; Sonja M. Best; Marshall E. Bloom (Immunologic Research, 2009)

The effects of beta-alanine supplementation and high-intensity interval training on neuromuscular fatigue and muscle function - Abbie E. Smith; Jordan R. Moon; Kristina L. Kendall; Jennifer L. Graef; Christopher M. Lockwood; Ashley A. Walter; Travis W. Beck; Joel T. Cramer; Jeffrey R. Stout (European Journal of Applied Physiology, 2009)

Estimating body fat in NCAA Division I female athletes: a five-compartment model validation of laboratory methods - Jordan R. Moon; Joan M. Eckerson; Sarah E. Tobkin; Abbie E. Smith; Christopher M. Lockwood; Ashley A. Walter; Joel T. Cramer; Travis W. Beck; Jeffrey R. Stout (European Journal of Applied Physiology, 2009)

The New River, Virginia, muskellunge fishery: population dynamics, harvest regulation modeling, and angler attitudes - Travis O. Brenden; Eric M. Hallerman; Brian R. Murphy; John R. Copeland; Joseph A. Williams (Environmental Biology of Fishes, 2007)

Interactions between two co-dominant, invasive plants in the understory of a temperate deciduous forest - R. Travis Belote; Jake F. Weltzin (Biological Invasions, 2006)

Coselection for microbial resistance to metals and antibiotics in freshwater microcosms - Ramunas Stepanauskas; Travis C. Glenn; Charles H. Jagoe; R. Cary Tuckfield; Angela H. Lindell; Catherine J. King; J. V. McArthur (Environmental Microbiology, 2006)
Summary Bacterial resistances to diverse metals and antibiotics are often genetically linked, suggesting that exposure to toxic metals may select for strains resistant to antibiotics and vice versa. To test the hypothesis that resistances to metals and antibiotics are coselected for in environmental microbial assemblages, we investigated the frequency of diverse resistances in freshwater microcosms amended with Cd, Ni, ampicillin or tetracycline. We found that all four toxicants significantly increased the frequency of bacterioplankton resistance to multiple, chemically unrelated metals and antibiotics. An ampicillin‐resistant strain of the opportunistic human pathogen Ralstonia mannitolilytica was enriched in microcosms amended with Cd. Frequencies of antibiotic resistance were elevated in microcosms with metal concentrations representative of industry and mining‐impacted environments (0.01–1 mM). Metal but not antibiotic amendments decreased microbial diversity, and a weeklong exposure to high concentrations of ampicillin (0.01–10 mg l −1 ) and tetracycline (0.03–30 mg l −1 ) decreased microbial abundance only slightly, implying a large reservoir of antibiotic resistance in the studied environment. Our results provide first experimental evidence that the exposure of freshwater environments to individual metals and antibiotics selects for multiresistant microorganisms, including opportunistic human pathogens.

Resistance to apoptosis, increased growth potential, and altered gene expression in cells that survived genotoxic hexavalent chromium [Cr(VI)] exposure - Daryl E. Pritchard; Susan Ceryak; Keri E. Ramsey; Travis J. O'Brien; Linan Ha; Jamie L. Fornsaglio; Dietrich A. Stephan; Steven R. Patierno (Molecular and Cellular Biochemistry, 2005)

Nucleotide excision repair functions in the removal of chromium-induced DNA damage in mammalian cells - Travis J. O'Brien; Bradford R. Brooks; Steven R. Patierno (Molecular and Cellular Biochemistry, 2005)

Differential impact of ionic and coordinate covalent chromium (Cr)-DNA binding on DNA replication - Jamie L. Fornsaglio; Travis J. O'Brien; Steven R. Patierno (Molecular and Cellular Biochemistry, 2005)

Oxygen and Hydrogen Isotopic Signatures of Large Atmospheric Ice Conglomerations - J. Martinez-FrÍAs; A. Delgado; M. MillÁN; E. Reyes; F. Rull; D. Travis; R. Garcia; F. LÓPez-Vera; J. A. RodrÍGuez-Losada; J. A. Martin-Rubi; J. Raya; E. Santoyo (Journal of Atmospheric Chemistry, 2005)

Precipitation pulses and carbon fluxes in semiarid and arid ecosystems - Travis E. Huxman; Keirith A. Snyder; David Tissue; A. Joshua Leffler; Kiona Ogle; William T. Pockman; Darren R. Sandquist; Daniel L. Potts; Susan Schwinning (Oecologia, 2004)

16S rDNA library-based analysis of ruminal bacterial diversity - Joan E. Edwards; Neil R. McEwan; Anthony J. Travis; R. John Wallace (Antonie van Leeuwenhoek, 2004)

Using Multimedia Modeling to Expedite Site Characterization - Curtis Travis; Karen R. Obenshain; James T. Gunter; James L. Regens; Christopher Whipple (Environmental Science and Pollution Research, 2004)

Hatching asynchrony, survival, and the fitness of alternative adult morphs in Ambystoma talpoideum - Travis J. Ryan; Gordon R. Plague (Oecologia, 2004)

Population variation in opsin expression in the bluefin killifish, Lucania goodei : a real-time PCR study - R. C. Fuller; K. L. Carleton; J. M. Fadool; T. C. Spady; J. Travis (Journal of Comparative Physiology A, 2004)

Carbon isotope discrimination and foliar nutrient status of Larrea tridentata (creosote bush) in contrasting Mojave Desert soils - Erik P. Hamerlynck; Stanley D. Smith; Travis E. Huxman; Joseph R. McAuliffe (Oecologia, 2004)

Mechanisms of chromium-induced suppression of RNA synthesis in cellular and cell-free systems: Relationship to RNA polymerase arrest - Jian Xu; Francis C.R. Manning; Travis J. O'Brien; Susan Ceryak; Steven R. Patierno (Molecular and Cellular Biochemistry, 2004)

Induction of pro-apoptotic and cell cycle-inhibiting genes in chromium (VI)-treated human lung fibroblasts: Lack of effect of ERK - Susan Ceryak; Carla Zingariello; Travis O'Brien; Steven R. Patierno (Molecular and Cellular Biochemistry, 2004)

Intraspecific variation in retinal cone distribution in the bluefin killifish, Lucania goodei - R. C. Fuller; L. J. Fleishman; M. Leal; J. Travis; E. Loew (Journal of Comparative Physiology A, 2003)

Refining the Whooping Crane Studbook by Incorporating Microsatellite DNA and Leg‐Banding Analyses - Kenneth L. Jones; Travis C. Glenn; Robert C. Lacy; James R. Pierce; Natalie Unruh; Claire M. Mirande; Felipe Chavez‐Ramirez (Conservation Biology, 2002)
We sought to refine genetic management of the endangered Whooping Crane ( Grus americana ) population by developing comprehensive genetic pedigrees for the captive population. Improvements to the studbook were accomplished by addition of pedigree information derived from leg‐banding data on wild juvenile and founder similarity coefficients calculated from microsatellite DNA profiles to the original studbook pedigree. Incorporation of pedigrees derived from data on leg‐banding of wild juveniles did not greatly alter the previous relatedness structure of the captive population, but incorporation of microsatellite similarity coefficients produced a substantially different view of the population structure. Microsatellite data provided new information on shared founder genotypes and provided a new DNA–based studbook pedigree that will assist in genetic management of the Whooping Crane population.

Expression of the extrinsic 23-kDa protein of photosystem II in response to salt stress is associated with the K+/Na+ discrimination locus Kna1 in wheat - M.-J. Gao; J. Dvorak; R. Travis (Plant Cell Reports, 2001)

Limitations of Multimedia Models for Use in Environmental Decision Making - Curtis C. Travis; Karen R. Obenshain; James L. Regens; Chris G. Whipple (Environmental Monitoring and Assessment, 2001)

Bileaflet Aortic Valve Prosthesis Pivot Geometry Influences Platelet Secretion and Anionic Phospholipid Exposure - Brandon R. Travis; Ulla M. Marzec; Hwa Liang Leo; Takki Momin; Christine Sanders; Stephen R. Hanson; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2001)

Effects of glutathione on chromium‐induced DNA. Crosslinking and DNA polymerase arrest - Travis O'Brien; Jian Xu; Steven R. Patierno (Molecular and Cellular Biochemistry, 2001)

Changes in myosin heavy chain composition with heavy resistance training in 60- to 75-year-old men and women - Matthew J. Sharman; Robert U. Newton; Travis Triplett-McBride; Michael R. M. McGuigan; Jeffrey M. McBride; Arja Häkkinen; Keijo Häkkinen; William J. Kraemer (European Journal of Applied Physiology, 2001)

An In Vitro Study of the Hinge and Near-Field Forward Flow Dynamics of the St. Jude Medical® Regent™ Bileaflet Mechanical Heart Valve - Jeffrey T. Ellis; Brandon R. Travis; Ajit P. Yoganathan (Annals of Biomedical Engineering, 2000)

Dinucleotide microsatellite loci in a migratory wood warbler (Parulidae: Limnothlypis swainsonii ) and amplification among other songbirds - Kevin Winker; Travis C. Glenn; Gary R. Graves (Molecular Ecology, 1999)

Primers for the detection of Oryctes virus from Scarabaeidae (Coleoptera) - Nicola K Richards; Travis R Glare; Ioane Aloali’I; Trevor A Jackson (Molecular Ecology, 1999)

Cartilage proteoglycan degradation by a mouse transformed macrophage cell line is mediated by macrophage metalloelastase - M. J. Janusz; M. Hare; S. L. Durham; J. Potempa; W. McGraw; R. Pike; J. Travis; S. D. Shapiro (Inflammation Research, 1999)

The detection of precipitating antibodies in equine infectious anemia and partial purification of the antigen - James B. Henson; Travis C. McGuire; John R. Gorham (Archives of Virology, 1971)